High spatial variations of potential nitrification and N2O production across the Yangtze River and associated major tributaries - Caixia Lan; Qiuxun Lin; Mengting Qi; Yuxuan Fu; Guosen Zhang; Ye Li; Min Liu; Lijun Hou; Xiaofei Li (Water Research, 2026)

Diverse bioactive metabolites from Callicarpa longifolia var. floccosa: terpenoids, polyketide, and callilongiflocin A as a potent anti-inflammatory diterpenoid targeting IL-17/TNF-α/MAPK signaling with anti-psoriatic activity - Ting Liu; Xiao-Lu Wu; Lian-Chun Li; Lan-Fang Tan; De-Sheng Ning; Yu-Xia Fu; Zheng-Hong Pan (Phytochemistry, 2026)

Intergenerational toxicity of flonicamid in zebrafish: Immune-inflammatory stress as a driver of parental and offspring effects - Ruiqiang Fu; Hongli Liu; Liangang Mao; Lizhen Zhu; Chi Wu; Xingang Liu; Lan Zhang (Journal of Environmental Sciences, 2026)

Interface electronic Coupling-Migration and morphology control in NiMnSe Heterostructure: Synergistic sulfur doping and vacancy engineering for efficient water splitting and supercapacitors - Zhiwei Lu; Rao Fu; Xi Peng; Xiangyi Long; Yue Zhang; Yidian Yuan; Qiule Lu; Li Zhang; Minglei Yan; Jianshan Ye; Lan Zhang (Fuel, 2026)

Fluorine-doped PBA@FPO core-shell structure as bifunctional electrocatalyst for overall water splitting through electronic engineering synergy - Zhiwei Lu; Ke Chen; Rao Fu; Xiangyi Long; Peixin Jiang; Jinrui Wu; Yue Zhang; Yidian Yuan; Qiule Lu; Zhaodan Fu; Minglei Yan; Lan Zhang (Fuel, 2026)

Early-life supplementation of bovine Milk Osteopontin prevents adult obesity by elevating succinic acid and acting through its receptor GPR91 - Lan Liu; Yilei Lao; Zixin Zhang; Chenming Lin; Yeqing Zhou; Zhimin Zhang; Bo Lönnerdal; Zhijian Cai; Junfen Fu (Food Research International, 2026)

Evaluating an enhanced three-dimensional electrode system for the remediation of Cr(Ⅵ)-contaminated clay: Detoxification efficiency and soil resilience - Zihong Bian; Honghui Wu; Xinyi Lan; Yanran Wang; Tianxiang Tong; Xiaohua Fu; Yijie Zhu; Meiying Jia; Xiong Yang; Haiyin Xu; Yuanling Luo; Zhengyong Xu; et al. (Journal of Environmental Chemical Engineering, 2026)

Integrated widely targeted metabolomics and GC-IMS reveal dynamic flavor, nutritional, functional, and metabolic profiles in macadamia kernels during processing - Gangjun Guo; Xiuhua Lan; Wenting Xu; Fujun Miao; Jiarong Fu; Shangxuan Ma; Yuanmiao Wei; Xinghao Tu; Xiyong He (Food Chemistry, 2026)

Deep placement of reduced nitrogen input strengthens soil water–nitrogen coupling and root–shoot coordination to enhance grain yield in dryland maize - Fu Liu; Jing Ling; Lan Luo; Xiaozhou Li; Yunfei Ren; Yi Zhou; Xiangyang Zhao; Xiaogang Yin; Shikun Sun; Juan Han; Youcai Xiong; Yuncheng Liao; et al. (Field Crops Research, 2026)

Near-infrared light-triggered nitric oxide-enhanced chemodynamic and photothermal therapy on magnesium alloy implants in osteosarcoma - Yongtang Wang; Lan Chen; Zhanfeng Zhou; Yuhan Liang; Tong Zhang; Rongbang Sun; Yueling Tian; Yang Liu; Yifu Fu; Huihan Wang; Guang Feng; Jianhua Miao; et al. (Chemical Engineering Journal, 2026)

Enhanced electrochromic performance of Al-doped NiO films via magnetron sputtering: Experimental characterization and first-principles insights - Weike Zhang; Zeshi Wang; Zhenchao Liu; Lan Zhang; Huizhong Ma; Jinqiu Fu; Fei Wang (Chemical Engineering Journal, 2026)

Lignin carbon dots with engineered graphitic N and sp2 domains: Visible-light-driven oxidase-like activity and green fluorescence for smartphone-assisted dual-mode nitrite detection - Pengyu Hu; Longwen Lei; Chenglong Fu; Yi Wang; Haiming Li; Xing Wang; Zhiwei Wang; Lan Yao; Yanzhu Guo (Chemical Engineering Journal, 2026)

Unveiling the pathogenesis and therapeutic strategies of Alzheimer’s disease through cuproptosis - Shuangfeng Xu; Jing Mu; Zhifeng Wang; Jiao Yang; Daman Tian; Ting Shi; Junfeng Lan; Pengfen He; Zhihui Hao; Youchuan Fu; Liwei Xing; Jianzhou Ye; et al. (BioMetals, 2026)

Effects of the ecpA gene on the biological characteristics and pathogenicity of avian pathogenic Escherichia coli strain FJLY68 - Haiyu Chen; Zehua Jin; Chuchu Duan; Zuchen Song; Yanqing Cheng; Mengshi Chen; Chenggong Zhang; Yi Lan; Weihui Shen; Yu Fu; Rongchang Liu; Xintian Zheng (Veterinary Microbiology, 2026)

Targeting microglial TLR3–NF-κB/MAPK and JAK/STAT Axis: PEITC as a suppressor of poly (I:C)-induced neuroinflammation - Yi-Ching Lan; Yan-Ru Xiao; Yow-Wen Hsieh; Yih-Dih Cheng; Shu-Fen Peng; Fu-Shin Chueh; Hsu-Tung Lee; Yu-Sheng Hsieh; Wei-Cheng Jiang; Wen-Tsong Hsieh; Yu-Cheng Chou (Toxicology and Applied Pharmacology, 2026)

The hidden cost of green food packaging: Biodegradable plastics release more micro/nanoplastics and enhance PFAS co-exposure - Qiaozhi Zhang; Sheng Lan; Kan Jiang; Yongning Wu; Qi Zhang; WenJiabao Wen; Hongyan Li; Linglin Fu (Journal of Hazardous Materials, 2026)

Averageness is not enough: Different perceptual codes for body attractiveness versus typicality - Zihan Zhu; Xiaolan Fu; Lan Chen; Chang Hong Liu; Connor J. Parde; Ying Hu (Evolution and Human Behavior, 2026)

Source Transition and Health Implication of PM2.5-Bound Metals: Multi-year High-resolution Observation in a Coastal Megacity - Yanjie Lei; Ming Hu; Yuankai Xie; Anja H. Tremper; Yue Liu; Lan Hong; Xin Cheng; Cheng Huang; Qingyan Fu; Jialiang Feng; David C. Green; Longhua Wu; et al. (Atmospheric Environment, 2026)

Biocontrol mechanism of Streptomyces sp. MEPF0303 against Sclerotium delphinii causing Dendrobium officinale southern blight revealed by multi-omics analysis - Qiao Liu; Yu-Jie Chen; Jing Shi; Yong-Jing Zhang; Hai-Lan Fu; Zi-Ling Tao; Tao Zhou; Zhi-wu Tan; Ji-Luan Zhang; Ji-Hong Jiang; Lu-Dan Li (Pesticide Biochemistry and Physiology, 2026)

Interactive effect between different growth duration variety and cutting height on grain yield and quality in ratoon rice - Jinjuan Zhu; Qimeng Lan; Xinchen Zhang; Hongshun Xiang; Yifan Fu; Huiping Wang; Changzai Zhou; Chen Yang; Guodong Yang; Xing Yu; Chang Zheng; Shen Yuan; et al. (Field Crops Research, 2026)

Corrigendum to “Effects of the ecpA gene on the biological characteristics and pathogenicity of avian pathogenic Escherichia coli strain FJLY68” [Vet. Microbiol. (2026) 111145] - Haiyu Chen; Zehua Jin; Chuchu Duan; Zuchen Song; Yanqing Cheng; Mengshi Chen; Chenggong Zhang; Yi Lan; Weihui Shen; Yu Fu; Rongchang Liu; Xintian Zheng (Veterinary Microbiology, 2026)

A 44-min periodic radio transient in a supernova remnant - Di Li; Mao Yuan; Lin Wu; Jingye Yan; Xuning Lv; Chaowei Tsai; Pei Wang; Jiaqi Zhao; Weiwei Zhu; Li Deng; Ailan Lan; Renxin Xu; et al. (Science Bulletin, 2026)

Grazing season overrides intensity in driving plant subordinate species-mediated community dynamics across contrasting elevations of typical steppe - Yu-Wen Zhang; Lan Li; Zhao-Xia Guo; Zhao-Ling Da; Wen-Jun Wang; Xing-Qi Wang; Fu-Jiang Hou; Ji-Zhou Ren (Global and Planetary Change, 2026)

Zwitterionic engineering of chitosan enables highly soluble, antibacterial films for sustainable fruit preservation - Dahai Liu; Xiaoxiao Wang; Jing Xu; Fang Yang; Riwang Li; Qiang Fu; Jie Li; Jieyan Wang; Xiu Wang; Haotian Lan; Ziyin Liu; Yafei Su; et al. (Food Research International, 2026)

Wheat-spike-shaped arabinans from Lycium barbarum by alkaline scission-Cascade refinement and its dual-immunomodulatory activity - Wenqi Huang; Yusong Zuo; Xiangyu Fu; Zhichun Yang; Yongqin Liao; Lan Zhang; Wenxian Lan; Shan Liu; Linjuan Huang; Zhongfu Wang; Hong Zhang; Guiping Gong (Food Chemistry, 2026)

An integrated γ-aminobutyric acid–phytic acid strategy mitigates oxidative stress and quality deterioration in spinach during ambient-temperature storage - Shiai Zeng; Lan Gao; Kai Wang; Xuwei Liu; Peihong Fu; Lin Li; Lei Zhao (Food Bioscience, 2026)

Precision measurement of the Ds*+-Ds+ meson mass difference - M. Ablikim; M.N. Achasov; P. Adlarson; X.C. Ai; R. Aliberti; A. Amoroso; Q. An; Y. Bai; O. Bakina; Y. Ban; H.-R. Bao; V. Batozskaya; et al. (Science Bulletin, 2026)

New alkaloids from the marine-derived fungus Penicillium sp. SWMU-WZ04-5 and their cytotoxic activity - Sijing Liu; Jinghao Cui; Mengyu Zhang; Ting Chen; Fengjian Lan; Xiujuan Fu; Siwei Chen; Dan Zhang; Ying Zhang; Hui Lei (Phytochemistry Letters, 2026)

Strong and liquid-free ion-conductive elastomer reinforced by chemically cross-linked cellulose network for strain sensors and triboelectric nanogenerators - Meilin Zhang; Zhongshen Cai; Yufan Lan; Zongming Lv; Rui Qian; Zhongsheng Shi; Lihua Fu; Baofeng Lin; Chuanhui Xu; Qunyang Li; Bai Huang (Chemical Engineering Journal, 2026)

Sevoflurane activates ATF4/NSUN7/PRKCD axis to induce neurotoxicity and cognitive impairment by promoting neuron mitochondrial fission - Qiang Fu; Ling Chen; Xiong Zeng; Cuilin Lan; Guanhua Wang; Shujia Li; Tingmin Lv; Hanwen Chen (Chemico-Biological Interactions, 2026)

Toxicological effects of polypropylene nanoparticles similar in size to nanoplastics in plastic-bottled injections on mice and zebrafish - Hui-Min Sun; Jie Wang; Xian-Fu Wu; Zhong-Lan Chen; Hui-Ying Yang; Zhi Lin; Shuang-Xing Li; Zhe Qu; Hua Chen; Shang-Chen Yao (Science of The Total Environment, 2026)

Unveiling potential water and land resource pressures under the electrolytic hydrogen boom in China - Yilin Li; Jichao Fu; Mingkai Liu; Bin Chen; Xingying Lan; Chunming Xu (Resources, Conservation and Recycling, 2026)

Suppression of lipid oxidation in frozen unwashed surimi by polyphenols-extract of foods: Investigating the synergistic mechanism of targeting hemoglobin and key radical-producing enzymes - Guiyuan Xiang; Jiangtao Li; Zhao Long; Jianan Zhang; Xiangjin Fu; Tianqing Lan; Kangzi Ren; Amna Jabeen (Food Bioscience, 2026)

Magnetic CO2-responsive aerogels with Ag/Fe MOF-derived carbon for adsorption and photo-Fenton-like degradation of organic pollutants - Anrong Yao; Xingwei Fu; Qian Xu; Chang Liu; Yunbo Mo; Qinglan Xue; Jiaojiao Shang; Jianwu Lan; Shaojian Lin (Desalination, 2026)

Two-dimensional mesoporous titania at hectogram level assembled on liquid interface as efficient zinc anode protector - Tong Fu; Bingxian Chu; Wanhai Zhou; Yu Hao; Rongyao Li; Zirui Lv; Lu Liu; Yalin He; Wendi Wang; Lanhao Yang; Kun Lan (Chemical Engineering Journal, 2026)

Magnetically oriented chitin/C-Fe-MOF composite hydrogel with high toughness and conductivity for advanced soft electronics - Liqin Cai; Xiang Shao; Xinghuai Mao; Yaming Fu; Yuxi Wu; Xiaoli Zhang; Lan Hu; Shujun Zhou; Yangjian Cheng; Huaqiang Sun; Yuying Zheng (Carbohydrate Polymers, 2026)

Effects of snowmelt runoff process on soil erosion in seasonal frozen districts - Renjie Hou; Lan Luo; Qiang Fu; Tianxiao Li; Anshuang Su; Miao Wang; Hai Xu; Jian Zhang; Yunping Yang; Qinglin Li (CATENA, 2026)

Tarsus-enriched chemosensory proteins in Achelura yunnanensis (Lepidoptera, Zygaenidae) and their interactions with pesticides - Fu-Peng Li; Zi-Hui Liu; Xiao-Rong Xiong; Jin-Lan Zhang; Hai-Yan Xiao; Nai-Yong Liu (Pesticide Biochemistry and Physiology, 2026)

Can protected area networks effectively conserve ecosystem services at the landscape scale? Evidence from Wuyishan Biodiversity Priority Conservation Area, China - Tianqi Fu; Yue Cao; Siren Lan; Le Yu; Lingyun Liao (Ecosystem Services, 2026)

Multilevel causal mechanisms of mineral-microbe interactions driving nitrogen cycling - Tianyu Shi; Zhiyong Zhang; Jianghui Feng; Zhikun Zou; Yang Huo; Huachun Lan; Huichun Zhang; Baoling Yuan; Ming-Lai Fu (Chemical Engineering Journal, 2026)

Electrochemical aptamer sensor based on nanocomposites composite material for rapid on-site detection of enrofloxacin in aquaculture - Bo Long; Qi Liu; Yizhuan Li; Qiongqiong Xing; Chuxiong Lan; Rui You; Liying Deng; Fangfang Qu; Meng An; Yingchun Fu; Shenghang Zhang; Dapeng Ye; et al. (Chemical Engineering Journal, 2026)

Mechanistic insights into phenolic compounds removal in constructed wetlands: efficiency comparison, synergistic interactions, and future optimization - Zigeng Yu; Zhiyong Zhang; Zhikun Zou; Tianyu Shi; Yang Huo; Huachun Lan; Baoling Yuan; Ming-Lai Fu (Bioresource Technology, 2026)

Unveiling the mechanisms of mechanical stirring for enhanced performance and stability of algal-bacterial flocs treating low C/N synthetic wastewater - Jun-Jie Gu; Bin-Di Mao; Xiao-Xiao Dou; Bin-Xin Zhang; Jia-Wei Xu; Chun-Wan Fu; Bang-Jie Lan; Xin-Jie Zhang; Zhe Xu; Feng Gao (Bioresource Technology, 2026)

Nitrogen-phosphorus co-doped carbon layer-confined ultra-thin self-grown polyphase molybdates heterojunction nanosheet arrays for efficient water splitting - Lan Zhang; Rao Fu; Ke Chen; Xi Peng; Li Zhang; Minglei Yan; Chun Wu; Mengmeng Sun; Gehong Su; Yanying Wang; Jianshan Ye; Hanbing Rao; et al. (Fuel, 2026)

Smartphone app-enabled dual-mode fluorescence and colorimetric portable sensors using RB@BSA-AuNRs for quality identification of plant-derived products - Hengye Chen; Xueqing Zeng; Guanghua Lei; Yun Huang; Wanjun Long; Wei Lan; Yuting Guan; Haiyan Fu (Food Research International, 2026)

Comparative study on the ecotoxicity of nanoformulated and conventional emamectin benzoate to Raphidocelis subcapitata: A mechanistic disparity analysis - Jin Yang; Yiming Chang; Ruiqiang Fu; ManLi Yu; Lan Zhang; Liangang Mao; Lizhen Zhu; Chi Wu; Yanning Zhang; Xingang Liu (Environmental Pollution, 2026)

Green upcycling of tigogenin from sisal waste: Chemoenzymatic cascade synthesis of progesterone derivatives as an alternative to traditional steroid production processes - Lu Song; Zhi-Kun Luo; Fu-Cheng He; Lan-Ya Huang; Liang-Bin Xiong; Yong-Jun Liu; Dong-Zhi Wei; Feng-Qing Wang (Chemical Engineering Journal, 2026)

Enhancing urban bird corridor identification by integrating three-dimensional factors: A validation with citizen science data - Yaling Huang; Ziru Chen; Yankai Huang; Tongyan Li; Chengyu Ran; Ying Lin; Yinghong Ding; Deng Pan; Yuxiang Lan; Jiali Jin; Zhipeng Zhu; Weicong Fu (Urban Forestry & Urban Greening, 2026)

Design and experimental synthesis of VOx/SSZ-13 catalyst based on first principles calculations - elucidating the role of VOx microstructure and valence state in propane dehydrogenation - Yan Liu; Tianle Zhang; Jinghui Yang; Jianchao Dong; Zixuan Fu; Changqing Chu; Yan He; Liancheng Bing; Xingying Lan; Junguo Li; Changning Wu; Dong-dong Hao; et al. (Journal of Environmental Chemical Engineering, 2026)

Hydroxysafflor yellow A from safflower enhances stress resilience and proteostasis in Caenorhabditis elegans - Linyao Jing; Zhaoxin Zhang; Zhixia Zhang; Yimeng Xu; Jing Tian; Xueqi Fu; Lan Yu; Jing Chen; Junfeng Ma (Food Research International, 2026)

Association of arsenic exposure with adverse birth outcomes: A meta-analysis and a benchmark dose analysis - Haoqi Jia; Nan Jing; Zhaomin Zhong; Xiaole Zhu; Tongbo Jin; Qianlei Yang; Yuanjie Wei; Yuanhui Zhu; Tingxu Jin; Lan Lan; Ying Mei; Huai Hu; et al. (Environmental Research, 2026)

Microbial electrochemical buffer zones enable PFAS detoxification and hidden risk mitigation in reclaimed water - Fuzhi Chen; Zhiyong Zhang; Boda Ouyang; Zhikun Zou; Jiuming Hu; Ming-Lai Fu; Huachun Lan; Baoling Yuan (Bioresource Technology, 2026)

Design and synthesis of stilbene analogs based on resveratrol as NF-κB inhibitors for the treatment of breast cancer - Shaojuan Fu; Yu Zhang; Yuanli Yang; Xing Lu; Yanni Wang; Lingling Lei; Junjie Lan; Huan He; Silong Zhang; Weidong Pan (Molecular Diversity, 2026)

Cervical spondylotic myelopathy caused by cervical dystonia: a case report - Shuang Li; Maolin Fu; Yuan Gao; Ke Li; Runnu Jin; Lan Wen (Acta Neurologica Belgica, 2026)

Visual toxicity of imidacloprid in zebrafish: Unraveling the pathways from ocular morphology to behavior via phototransduction dysregulation - Ruiqiang Fu; Hanfei Zheng; Han Gao; Liangang Mao; Chi Wu; Lizhen Zhu; Xingang Liu; Lan Zhang (Journal of Hazardous Materials, 2026)

Photothermal-activated self-healing MXene hydrogel for diabetic wound healing with polyphenol synergy - Siqi Ye; Dan He; Tao Chen; Keng-Fu Lan; Yongjin Zhong; Yancheng Lai; Yingying Wu; Anchun Mo (Chemical Engineering Journal, 2026)

Associations of Insulin Sensitivity with Risk of All-Cause and Cause-Specific Dementia: A Prospective Cohort Study - Yan Fu; Pei-Yang Gao; Wei Xu; Lan Tan (Molecular Neurobiology, 2026)

miR‑16‑5p Protects RGCs Against Retinal Ischemia–Reperfusion Injury by Modulating Astrocyte-Mediated Neuroinflammation Through the Wip1/NF-κB Signaling Axis - Wen Hu; Wenjing He; Guangyi Huang; Yuchen Zhou; Yue Li; Shuya Tao; Daizai Lei; Fen Tang; Ningning Tang; Li Jiang; Qiangqiang Lan; Hui Huang; et al. (Molecular Neurobiology, 2026)

Byakangelicol Alleviates Ischemic Brain Injury by Inhibiting Microglial Activation and Oxidative Stress - Xiao Wan Wang; Yan Qiong Fu; Zhuo Li Li; Ting Li; Hui Lan Wang; Yu Zheng; Chan Zhang; Miaolin Zeng; Chan Li; Dewei Xie; Bai Hui Chen (Molecular Neurobiology, 2026)

Proteins Associated with Cognition in Amyloid-beta Positive Elders Based on Cerebrospinal Fluid Proteomics - Min Liu; He-Ying Hu; Yan Fu; Hao-Chen Chi; Liang-Yu Huang; Lan Tan; Hao Hu (Molecular Neurobiology, 2026)

Corrigendum to “Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells” [Vet. Microbiol. 310 (2025) 110723] - Kui Xu; Yu-Ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

High-resolution spatial mapping of electrocorticographic activities with NeuroCam: a 4096-channel, multiplexed flexible thin-film transistor array - Yang Xie; Zepeng Zhang; Muyang Liu; Jinhong Guo; Miao Xu; Lei Zhou; Lei Zhang; Lihao Yao; Xiaolin Zhou; Zhengwei Hu; Liang Ma; Xiaojian Li; et al. (Science Bulletin, 2025)

Comprehensive fatigue assessment in deep-sea enclosed cabins using optimized multi-dimensional weighting - Wei-lan An; Jing Chen; Jin-chi Fu; Zhao-xian Ren; Deng-kai Chen (Ocean Engineering, 2025)

Presence of a queen (Apis mellifera) reduces the sensitivity of worker bees to environmental risks - De Fang Niu; Qiu Lan Zheng; Bin Yuan; Xiao Ling Su; Cui Ping Zhang; Yuan Yuan Lu; Ping Liu; Fu Liang Hu; Huo Qing Zheng (Journal of Asia-Pacific Entomology, 2025)

Theoretical investigation on desalination performance investigation of functionalized AB-COF membranes - Ming Wu; Zihang Zhao; Chengyi Lan; Lei Ye; Sirun Xie; Disheng Yang; Yikai Fu; Lijun Liang (Desalination, 2025)

Cryogenic pre-activation induces structural optimization and performance boost for Li-rich Mn-based cathodes - Rui-Chi Li; Lan-Fang Que; Jun-Sen Jiang; Fu-Da Yu; Ji-Huai Wu; Xuan Wang; Can-Zhong Lu; Yi-Ming Xie (Chemical Engineering Journal, 2025)

Araloside A Induces Raf/MEK/ERK-Dependent Autophagy to Mitigate Alzheimer’s and Parkinson’s Pathology in Cellular and C. elegans Models - Xue Chen; Xing-Yue Zhou; Cai Lan; Hai-Jun Fu; Zhi-Chao Li; Meng-Yi Chen; Yong-Ping Wen; Lu Yu; Da-Lian Qin; An-Guo Wu; Jian-Ming Wu; Xiao-Gang Zhou (Molecular Neurobiology, 2025)

Myosin heavy chain 9 is a critical host factor for Japanese encephalitis virus entry and replication in U251 cells - Kui Xu; Yu-ke Xu; Jia-Fei Zhan; Lei Yuan; Ya-Lan Feng; Rong Huang; Yung-Fu Chang; Zhuang Zhu; Xiao-Yao Yang; Li-Yao Deng; Yang Deng; Yang Ren; et al. (Veterinary Microbiology, 2025)

Microplastics: an overlooked particle organic carbon in river systems - Xuke Liu; Weijian Zhou; Peng Cheng; Fei Zhang; Liangcheng Tan; Yunchong Fu; Yukun Fan; Jianghu Lan; Huachun Gu; Wen Liu; Ting Wang (Science Bulletin, 2025)

The protein kinase MLOP1 mediates pectin fragment signaling and feedback regulation of cell wall synthesis - Xiaohui Liu; Jingjing Sha; Qingyao Li; Shuai Yuan; Jialin Tao; Shihan Fu; Pu Gan; Qiuyan Lan; Johannes Liesche; Chaowen Xiao (Journal of Plant Physiology, 2025)

Enabling high-performance aqueous Zn batteries with sub-zero temperatures surpassing room temperature combining cosolvent engineering and redox regulation strategy - Qiong Li; Ganghui Wei; Ni Lan; Yanzheng Li; Libo Wang; Xinyu Zhang; Yujun Fu; Qiming Liu; Yonggang Zhao; Deyan He (Chemical Engineering Journal, 2025)

Dismembered Guadalupian (Middle Permian) seamounts within the Yarlung-Tsangpo Suture Zone: Implications for the opening time of the Neo-Tethys Ocean - Hong-fu Zhou; Yi-chun Zhang; Mao Luo; Xin Li; Hua Zhang; Hai-peng Xu; Ruo-lan Liao; Qi Ju; Xiao-Hui Cui; Jun-jie Liu; Yao-feng Cai; Shu-zhong Shen (Palaeogeography, Palaeoclimatology, Palaeoecology, 2025)

Algal-bacterial symbiosis strengthens the treatment of high-salinity phenolic wastewater and its molecular mechanism - Xiao-Xiao Dou; Bin-Di Mao; Ang Li; Jun-Jie Gu; Xiao-Ling Zhang; Chun-Wan Fu; Xin-Jie Zhang; Bang-Jie Lan; Jia-Wei Xu; Bin-Xin Zhang; Hong-Jie Zheng; Feng Gao (Journal of Hazardous Materials, 2025)

Synergistic highly sensitive electrochemical detection of enrofloxacin using Eichhornia crassipes-derived carbon dots and molecularly imprinted polymer networks - Chang-Hong Wang; Yi-Yue Tang; Yan-Jun Li; Fu-Lan Xiao; Lian-Di Zhou; Qi-Hui Zhang; Chun-Su Yuan (Journal of Environmental Chemical Engineering, 2025)

System characteristics of integrated continuous flow simultaneous partial Nitrification, Anammox and Denitrification (SNAD) for NH4+-rich wastewater: performance, sludge evolution, metagenomic sequencing analysis - Peng-fei Yu; Ding Wang; Xing-guan Ma; Yu-bo Fu; Li-yao Han; Ao Wang; Dian-lin Jiang; Hai-wen Sun; Dong-xue Li; Xing Jin; Kang-da Yang; Li-cheng Zhang; et al. (Environmental Research, 2025)

A porous calcium alginate aerogel of surface hydroxylated MOF-801 for enhancing solar-driven atmospheric water harvesting - Cai-Hua Liu; Lei Xu; Zhen-Yu Wang; Zhiyong Zhang; Huachun Lan; Ming-Lai Fu; Baoling Yuan (Chemical Engineering Journal, 2025)

Bisphenol A caused abnormal spermatogenesis of Eriocheir sinensis through es-ERR/es-KIF4A pathway with discussion of BPA substitutes - Yu Yang; Di Wu; Tian Lei; Hang-Yuan Zhao; Jun-Jie Yu; Lan-Min Wang; Ding-Xi Liu; Yan-Shuang Zhao; Jia-Hao Ni; Fu-Qing Tan; Wan-Xi Yang (Journal of Hazardous Materials, 2025)

Wheat stripe rust resistance gene Yr9, derived from rye, is a CC-NBS-LRR gene in a highly conserved NLR cluster - Yang Yu; Jiajun Liu; Shengjie Lan; Qihang Chen; Jinlong Li; Haoyuan Song; Chen Pan; Juan Qi; Yu Cui; Xingfeng Li; Ming-Cheng Luo; Fei Ni; et al. (Science China Life Sciences, 2025)

Robustness of neuro-evolution in urban drainage system control under communication failures: comparing centralized and decentralized control schemes - Shengwei Pei; Guangtao Fu; Lan Hoang; David Butler (Water Research, 2025)

Novel one-step solid-state synthesis of 2D Ni/C for efficient electro/photo-catalytic hydrogen evolution - Heng Ke; Yaya Xie; Yi Luo; Yinhong Gao; Lan Yin; Jun Fu; Liangzhe Chen (Fuel, 2025)

A nanozyme colorimetric sensor combined with cloud-based machine learning algorithm-assisted WeChat mini program for intelligent identification of Chinese green tea - Wanjun Long; Siyu Wang; Yangcheng Ling; Yuting Guan; Huiru Zhang; Hengye Chen; Wei Lan; Yuanbin She; Haiyan Fu (Food Research International, 2025)

A novel hybrid machine learning approach for accurate retrieval of ocean surface chlorophyll-a across oligotrophic to eutrophic waters - Ting Qin; Tianlong Liang; Donglin Fan; Hongchang He; Guiwen Lan; Bolin Fu (Environmental Research, 2025)

Sequential hydrothermal liquefaction of lignocellulose-rich livestock manure: A new perspective on enhancing the production and quality of low-phenolic biocrude - Siyuan Long; Pengxin Yu; Jianrong Huang; Conghao Ku; Xinge Miao; Junjie Lan; Hao Fu; Chunbao Charles Xu; Haiwei Jiang; Zhengli Liu; Weiran Yang (Bioresource Technology, 2025)

Quantitative assessment of the carbon dioxide absorption capacity of vegetation in China, 2000–2020 - Guoxin Lan; Zhuangzhuang Hou; Yan Wu; Bin Yan; Chuan Fu; Yi Jiang; Xiang Wang; Qiushi Zheng (Environmental Science and Pollution Research, 2025)

Phosphate-solubilizing bacteria facilitate rhizospheric processes of Bidens pilosa L. in the phytoremediation of cadmium-contaminated soil: Link between phosphorus availability and cadmium accumulation - Yi Li; Shiyu Luo; Yiyun Fu; Chijian Tang; Xiaoxiao Qin; Dongyi Shi; Wei Lan; Yingxuan Tang; Fangming Yu (Journal of Hazardous Materials, 2025)

Smartphone app with cloud-based machine learning and visual sensor array for instrument-free detection of species, geographic origin, and quality marker in functional food Gancao - Yun Huang; Aifen Hu; Lixue Ren; WanJun Long; Wei Lan; Yi He; Yuanbin She; Hengye Chen; Haiyan Fu (Food Control, 2025)

Binders with cationic semi-interpenetrating networks for sodium-ion batteries under extreme conditions - Chen-Hui Yang; Chi-Hon Leung; Lan-Fang Que; Fu-Da Yu; Can-Zhong Lu; Yi-Ming Xie (Chemical Engineering Journal, 2025)

Air pollution of PM2.5-bound PAHs in urban Chongqing, China from 2015 to 2022: Concentration, source tracking and health risk - Bofei Fu; Shang Li; Shushu Lan; Xiaowei Peng; Chongjun Ran; Nanyan Li; Hong Li; Lun Xiao; Guohua Zhao; Junrui Chang; Jingxiu Han; Yunyun Wu; et al. (Urban Climate, 2025)

Potential impacts of polyethylene microplastics and heavy metals on Bidens pilosa L. growth: Shifts in root-associated endophyte microbial communities - Ziang He; Yanxue Wang; Yiyun Fu; Xiaoxiao Qin; Wei Lan; Dongyi Shi; Yingxuan Tang; Fangming Yu; Yi Li (Journal of Hazardous Materials, 2025)

Green construction and digestive properties of Fe (II) and quercetin double-loaded delivery system by wampee polysaccharide and its application - Juan-li Fang; Fu-lan Hu; Ya-qin Wu; Tao Liu; Peng-peng Sun; Yuan-yuan Ren (Food Chemistry, 2025)

The nickel hyperaccumulator Odontarrhena chalcidica (Brassicaceae) preferentially takes up zinc over nickel - Ya-Zhou Wang; Ke-Rui Geng; Bing-Lan Mo; Ting Liu; Ye-Tao Tang; Dian Wen; Fu-Rong Li; Xu Wang; Lei Li; Rui-Ying Du; Antony van der Ent; Teng-Hao-Bo Deng; et al. (Plant and Soil, 2025)

A Year Marked by Extreme Precipitation and Floods: Weather and Climate Extremes in 2024 - Wenxia Zhang; Tianjun Zhou; Wanheng Ye; Tingyu Zhang; Lixia Zhang; Piotr Wolski; James Risbey; Zhuo Wang; Seung-Ki Min; Hamish Ramsay; Michael Brody; Alice Grimm; et al. (Advances in Atmospheric Sciences, 2025)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2025)

Arsenic Accumulation in Different Parent Materials of Rice (Oryza Sative L.) are Affected by Root Morphology - Yi Chen; Dehui Tu; Deqiang Li; Yinggang Xu; Yueyi Wu; Zhaoyong Zeng; Xiaoyan Tang; Yang Li; Chaorui Yan; Ting Lan; Fu Huang; Xuesong Gao; et al. (Journal of Plant Growth Regulation, 2025)

Dual-enzyme inhibitor screening against α-glucosidase and PTP1B by hollow fibers in tandem with ultrafiltration - Yan Shi; Renjie Fu; Jiayi Chen; Hui Lan; Boyang Yu; Jin Qi (Analytica Chimica Acta, 2025)

Adsorption characteristics of sulfate reducing bacteria Clostridium sp. on lignite surface - Huan He; Zi Yang Zhou; Di Zhan; Yong Zhang; Wen Cheng Xia; Bo Fu; Feng Juan Lan; Xiu Xiang Tao; Zai Xing Huang (Environmental Science and Pollution Research, 2025)

Energy production and denitrogenation performance by sludge biochar based constructed wetlands-microbial fuel cells system: Overcoming carbon constraints in water - Boda Ouyang; Zhiyong Zhang; Fuzhi Chen; Fei Li; Ming-Lai Fu; Huachun Lan; Baoling Yuan (Water Research, 2025)

Comprehensive characterization of micro-pore structures in different lithologies of the lacustrine fine-grained mixed sedimentary reservoir of the Shahejie Formation in the Jiyang Depression - Wenneng Zhao; Mingshi Feng; Yanyu Gao; Ying Fu; Wanbin Meng; Siyuan Fan; Yi Lan; Bing Zhang (Ore and Energy Resource Geology, 2025)

Optimizing the thiosulfate-mediated zerovalent iron/persulfate activation systems: Trade-off between Fe(III)/Fe(II) cycling and quenching effects in environmental remediation - Maolin Wang; Mi Deng; Gang Zhao; Yanchun Fan; Tianwen Liu; Ying Huang; Lan Peng; Haoyang Fu; Shengqiong Fang (Journal of Environmental Management, 2025)

Atomically dispersed bimetallic single-atom Cu, Fe/NC as pH-universal ORR electrocatalyst - Weiming Gong; Peng Guo; Lan Zhang; Rao Fu; Minglei Yan; Chun Wu; Mengmeng Sun; Gehong Su; Yanying Wang; Jianshan Ye; Hanbing Rao; Zhiwei Lu (Chemical Engineering Journal, 2025)

Exosomes derived from follicular fluid promote proliferation and suppress apoptosis of yak (Bos grunniens) granulosa cells by enhancing antioxidant capacity in vitro - Bangting Pan; Xupeng Li; Qinhui Yang; Yumian Xie; Zhuo Chen; Jun Yu; Honghong He; Yan Xiong; Wei Fu; Shi Yin; Daoliang Lan; Jian Li; et al. (Animal Reproduction Science, 2025)

Effective analysis of thyroid toxicity and mechanisms of acetyltributyl citrate using network toxicology, molecular docking, and machine learning strategies - Yujian Lan; Qingping Peng; Bowen Fu; Huan Liu (Toxicology, 2025)

Facile access to spirobifluorene-fused chiral multi-resonance materials with ultra-narrowband blue emission - Hu Cheng; Chen-Hao Guo; Meng Li; Yusong Guo; Zhangyi Fu; Junjie Liu; Yudong Yang; Jingbo Lan; Zhengyang Bin (Science Bulletin, 2025)

Catalytic detoxification of mitoxantrone by graphitic carbon nitride (g-C3N4) supported Fe/Pd bimetallic nanoparticles - Qianyu Xu; Haoyang Fu; Jiyuan Gu; Liyu Lei; Lan Ling (Journal of Environmental Sciences, 2025)

On using an aerosol thermodynamic model to calculate aerosol acidity of coarse particles - Zhengyang Fang; Shuwei Dong; Chengpeng Huang; Shiguo Jia; Fu Wang; Haoming Liu; He Meng; Lan Luo; Yizhu Chen; Huanhuan Zhang; Rui Li; Yujiao Zhu; et al. (Journal of Environmental Sciences, 2025)

Coal dust combustion suppression via melamine polyphosphate and silica: Experiment and simulation - Shuang Geng; Ting Zhang; Xin Zhang; Shaoqian Cheng; Guoen Fu; Jianfu Xu; Wen Zhou; Yanhua Lan; Xueqiang Shi; Chi-Min Shu; Weiguo Cao (Fuel, 2025)

Mitochondrial genomes reveal low genetic diversity in snow leopards - Shiqing Wang; Haimeng Li; Yinping Tian; Yu Lin; Yingna Zhou; Jan E. Janecka; Yuan Fu; Yue Ma; Zhen Wang; Tianming Lan (Conservation Genetics, 2025)

Mitochondria-targeted antioxidant MitoQ improves the quality of low temperature-preserved yak semen via alleviating oxidative stress - Yanjin Zhu; Jun Yu; Qinhui Yang; Yumian Xie; Xupeng Li; Zhuo Chen; Yan Xiong; Wei Fu; Honghong He; Shi Yin; Daoliang Lan; Jian Li; et al. (Animal Reproduction Science, 2025)

Trans-4-hydroxy-L-proline catabolism by Pseudomonadota in the ocean - Yan Wang; Zhen Wang; Wen-Xiao Zhao; Xiao-Jie Yuan; Yang Yu; Peng Wang; Min Wang; Andrew McMinn; Yu-Zhong Zhang; Ming Peng; Hui-Hui Fu; Xiu-Lan Chen (Marine Life Science & Technology, 2025)

Molecular characterization of MSX2 gene and its role in regulating steroidogenesis in yak (Bos grunniens) cumulus granulosa cells - Jun Ma; Gan Yang; Xuan Qin; Luoyu Mo; Xianrong Xiong; Yan Xiong; Honghong He; Daoliang Lan; Wei Fu; Jian Li; Shi Yin (Theriogenology, 2025)

Human activities are intensifying the spatial variation of landslides in the Yellow River Basin - Naiman Tian; Hengxing Lan; Langping Li; Jianbing Peng; Bojie Fu; John J. Clague (Science Bulletin, 2025)

Dietary Iron Overload Triggers Hepatic Metabolic Disorders and Inflammation in Laying Hen - Yue Li; Lan-Xin Li; Han Cui; Wan-Xue Xu; Hong-Yu Fu; Jiu-Zhi Li; Rui-Feng Fan (Biological Trace Element Research, 2025)

Real-time multi-objective optimization of pump scheduling in water distribution networks using neuro-evolution - Shengwei Pei; Lan Hoang; Guangtao Fu; David Butler (Journal of Water Process Engineering, 2024)

Copper slag based catalytic material was prepared using a one-pot method to efficiently activate of peroxymonosulfate for degradation of carbamazepine - Cong Pan; Yunqiao Wang; Chenyang Fu; Jirong Lan (Journal of Environmental Chemical Engineering, 2024)

Cultural ecosystem services and disservices in protected areas: Hotspots and influencing factors based on tourists’ digital footprints - Qiaochun Gan; Lingyun Liao; Xin Kang; Zhenduo Xu; Tianqi Fu; Yue Cao; Yunshuang Feng; Jianwen Dong; Siren Lan (Ecosystem Services, 2024)

PANoptosis: a new insight for oral diseases - Xinyi Jiang; Tingting Fu; Lan Huang (Molecular Biology Reports, 2024)

The role of serum-glucocorticoid regulated kinase 1 in reproductive viability: implications from prenatal programming and senescence - Qiying Zhang; Ye Tian; Zhujing Fu; Shuangyu Wu; Huizhen Lan; Xuanle Zhou; Wendi Shen; Yiyun Lou (Molecular Biology Reports, 2024)
Objective Organisms and cellular viability are of paramount importance to living creatures. Disruption of the balance between cell survival and apoptosis results in compromised viability and even carcinogenesis. One molecule involved in keeping this homeostasis is serum-glucocorticoid regulated kinase (SGK) 1. Emerging evidence points to a significant role of SGK1 in cell growth and survival, cell metabolism, reproduction, and life span, particularly in prenatal programming and reproductive senescence by the same token. Whether the hormone inducible SGK1 kinase is a major driver in the pathophysiological processes of prenatal programming and reproductive senescence? Method The PubMed/Medline, Web of Science, Embase/Ovid, and Elsevier Science Direct literature databases were searched for articles in English focusing on SGK1 published up to July 2023 Result Emerging evidence is accumulating pointing to a pathophysiological role of the ubiquitously expressed SGK1 in the cellular and organismal viability. Under the regulation of specific hormones, extracellular stimuli, and various signals, SGK1 is involved in several biological processes relevant to viability, including cell proliferation and survival, cell migration and differentiation. In line, SGK1 contributes to the development of germ cells, embryos, and fetuses, whereas SGK1 inhibition leads to abnormal gametogenesis, embryo loss, and truncated reproductive lifespan. Conclution SGK1 integrates a broad spectrum of effects to maintain the homeostasis of cell survival and apoptosis, conferring viability to multiple cell types as well as both simple and complex organisms, and thus ensuring appropriate prenatal development and reproductive lifespan.

The development of novel genome-SSRs, multiplex PCR panels, and allelic ladders for parentage identification in Tachypleus tridentatus - Boyu Chen; Ju Long; Jinxia Liu; Pengliang Wang; Zihang Ma; Zhenyu Lan; Ziwei Liang; Qianni Fu; Zining Zhang; Yan Zhang; Yitao Duan; Peng Zhu; et al. (Aquaculture, 2024)

Integrative analysis of transcriptome and metabolome reveals the heterogeneity of ovarian follicles between high-altitude Yak (Bos grunniens) and Low-altitude cattle (Bos taurus) - Hongmei Xu; Zifeng Ma; Jinlun Lu; Yueyue Li; Qiao Li; Shi Yin; Honghong He; Yan Xiong; Xianrong Xiong; Jian Li; Daoliang Lan; Wei Fu (Livestock Science, 2024)

Metabolomics and microbiomics revealed the combined effects of different-sized polystyrene microplastics and imidacloprid on earthworm intestinal health and function - Huimin Fu; Lizhen Zhu; Lang Chen; Lan Zhang; Liangang Mao; Chi Wu; Yiming Chang; Jinhua Jiang; Hongyun Jiang; Xingang Liu (Environmental Pollution, 2024)

Blue room-temperature phosphorescent carbon dot composites with high quantum yield for information encryption and LED light emission - Shaowen Yang; Hongmei Zhang; Ke Jian; Liming Fu; Di Lan; Xihui Zhao (Chemical Engineering Journal, 2024)

Soluble Epoxide Hydrolase Inhibitor Ameliorates Olfactory Dysfunction, Modulates Microglia Polarization, and Attenuates Neuroinflammation after Ischemic Brain Injury - Chien-Fu Yeh; Tung-Yueh Chuang; Ming-Ying Lan; Yung-Yang Lin; Wei-Hao Huang; Yu-Wen Hung (Journal of Neuroimmune Pharmacology, 2024)

Hourly effect of atmospheric reactive nitrogen species on the onset of acute ischemic stroke: Insight from the Shanghai Stroke Service System Database - Kun Fang; Lan Hong; Yiran Zhang; Nan Cao; Jialiang Feng; Ming Hu; Qingyan Fu; Yang Zheng; Qundi Yang; Yuzhuo Wang; Jinyitao Wang; Shunyao Wang; et al. (Science of The Total Environment, 2024)

Evidence for archaeal metabolism of D-amino acids in the deep marine sediments - Yang Yu; Ning-Hua Liu; Zhao-Jie Teng; Yin Chen; Peng Wang; Yu-Zhong Zhang; Hui-Hui Fu; Xiu-Lan Chen; Yu-Qiang Zhang (Science of The Total Environment, 2024)

Female urinary incontinence in China after 15 years’ efforts: Results from large-scale nationwide surveys - Jiming Zhu; Haiyu Pang; Peicheng Wang; Yanhua Chen; Huihui Li; Qing Liu; Luwen Wang; Hangmei Jin; Liyan Gong; Jingyan Xie; Ting Lai; Aiyang Li; et al. (Science Bulletin, 2024)

Enhancing Chlorella vulgaris growth with Fe-loaded sulphoaluminate cement: A promising phosphorus adsorbent reutilization strategy - Faqin Lian; Qionglin Fu; Shiyu Miao; Yanyu Zhang; Ying Wang; Junfeng Wang; Huachun Lan; Huijuan Liu; Jiuhui Qu (Resources, Conservation and Recycling, 2024)

Dynamic disaster risk assessment of urban waterlogging on pedestrian flow by intelligent simulation of hydrodynamics coupled with agent-based models in Chao-yang river basin of Nanning, China - Huangkang Lan; Yunchuan Yang; Hao Fu; Haixiang Liao; Liping Liao; Shanqi Huang; Xungui Li (Stochastic Environmental Research and Risk Assessment, 2024)

Identification and Activity Study of an Impurity Band Observed in the nrSDS-PAGE of Aflibercept - Meng Li; Weiyu Li; Xin Wang; Gang Wu; Jialiang Du; Gangling Xu; Maoqin Duan; Xiaojuan Yu; Chunbo Cui; Chunyu Liu; Zhihao Fu; Chuanfei Yu; et al. (Pharmaceutical Research, 2024)

Applications of multi-omics techniques to unravel the fermentation process and the flavor formation mechanism in fermented foods - Linfeng Wen; Lixin Yang; Cong Chen; Jun Li; Jiangyan Fu; Guo Liu; Qixin Kan; Chi-Tang Ho; Qingrong Huang; Yaqi Lan; Yong Cao (Critical Reviews in Food Science and Nutrition, 2024)

Simultaneous removal of Cd(II) and phosphate by nanoscale zero-valent iron from solution: Co-sorption and implication of corrosion - Haoyang Fu; Jie Sheng; Chenliu Tang; Wei-xian Zhang; Lan Ling (Chemosphere, 2024)

Fruits’ cold tolerance: a review of mechanisms and methods - Jian-Lin He; Gang-Shuai Liu; Xiao-Dan Zhao; Lan-Ting Xiang; Shi-Yin Xie; Yun-Xiang Wang; Da-Qi Fu (Postharvest Biology and Technology, 2024)

Meta-omics analysis reveals the marine arsenic cycle driven by bacteria - Zhao-Jie Teng; Jian Li; Peng Wang; Chun-Yang Li; Ming Peng; Qi-Long Qin; Xiu-Lan Chen; Yin Chen; Hui-Hui Fu; Ning Wang; Yu-Zhong Zhang (Journal of Hazardous Materials, 2024)

A systematic investigation of peracetic acid oxidation and polymeric coagulants re-flocculation to enhance activated sludge dewatering: Multi-porous skeleton structures - Zhiyong Zhang; Chunxiao Liu; Boda Ouyang; Ming-Lai Fu; Lei Xu; Huachun Lan; Baoling Yuan (Journal of Environmental Management, 2024)

Reclassification of Streptomyces violarus (Artamonova and Krassilnikov 1960) Pridham 1970 as a Later Heterotypic Synonym of Streptomyces violaceus (Rossi Doria 1891) Waksman 1953 using a Polyphasic Approach - Pei-Lan Long; Yin-Feng Wang; Li Fu; Yan Xiao; Shan-Guang Tang; Jian Gao (Current Microbiology, 2024)

Klotho enhances diastolic function in aged hearts through Sirt1-mediated pathways - Nastaran Daneshgar; Renny Lan; Michael Regnier; Samuel G. Mackintosh; Ravinandan Venkatasubramanian; Dao-Fu Dai (GeroScience, 2024)

Derivatives of Br-doped metal-organic framework for improved acetaldehyde adsorption-photocatalytic oxidation - Jun Wang; Changqing Yang; Mingli Fu; Daiqi Ye; Lan Fan; Yun Hu (Science of The Total Environment, 2024)

Tomato NAC transcription factor NOR-like1 positively regulates tomato fruit softening - Zhen-Zhen Peng; Hong-Li Li; Gang-Shuai Liu; Xiao Su; Xiaodan Zhao; Donald Grierson; Lan-Ting Xiang; Jian-Lin He; Gui-Qin Qu; Hong-Liang Zhu; Ben-Zhong Zhu; Yun-Bo Luo; et al. (Postharvest Biology and Technology, 2024)

Genotoxicity and cytotoxicity evaluation of a heat-not-burn product - Fudong Fu; Xiaoyu Li; Younan Chen; Lan Li; Jiexiong Dou; Kun Liang; Yexian Chen; Yanrong Lu; Yuchuan Huang (Mutation Research - Genetic Toxicology and Environmental Mutagenesis, 2024)

Rapid visual detection of sulfur dioxide residues in food using acid-sensitive CdTe quantum dots-loaded alginate hydrogel beads - Wei Lan; Yanmin Rao; Xiangyu Zhao; Yi Zhao; Xinyi Min; Yue Wu; Ziyi Jiang; Ting Li; Yinhua Li; Hengye Chen; Wanjun Long; Yuanbin She; et al. (Food Chemistry, 2024)

“Edge in-situ heterogeneous” BiOI based on defect engineering and non-noble metal deposition: Boosting visible-light photocatalytic sterilization - Bangfeng Fu; Yifan Pan; Peng Zhao; Liang Zhang; Junchen Zhuo; Jianxing Feng; Bingzhi Li; Lenan Yao; Jiafeng Xi; Xi Lan; Linpin Luo; Ting Du; et al. (Chemical Engineering Journal, 2024)

Potential risk assessment of the large hydropower station dumpsite using numerical simulation: a case study in Shanxi Province, China - Dong-dong Li; Han-dong Liu; Zhong-fu Wang; Feng-lan Chen; Xiao-chao Li (Natural Hazards, 2024)

Performance evaluation of different reflected signal extraction methods on GNSS-R derived sea level heights - Chi–Ming Lee; Cheng–Yun Fu; Wen–Hau Lan; Chung–Yen Kuo (Advances in Space Research, 2024)

Exploring the hydrologic regulation and pollutant release of complex paddy systems in a large-scale agricultural catchment - Weixiang Li; Ziqian Zhu; Weiping Xiong; Bolin Zhou; Hongliang Hu; Jing Tong; Xin Li; Xiang Gao; Shuai Li; Wenxin Fu; Lan Lu; Zhaohui Yang; et al. (Journal of Hydrology, 2024)

Real-time control of urban drainage systems using neuro-evolution - Shengwei Pei; Lan Hoang; Guangtao Fu; David Butler (Journal of Environmental Management, 2024)

Against catalyst deactivation during toluene oxidation on CuCeOx in flue gas: High oxidation efficiency and rapid oxidation pathway - Ziyang Guo; Beilong Lin; Jiali Tang; Jinhang Yang; Lan Fan; Mingli Fu; Daiqi Ye; Yun Hu (Journal of Environmental Chemical Engineering, 2024)

Three-dimensional fluorescence combined with alternating trilinear decomposition and random forest algorithm for the rapid prediction of species, geographical origin and main components of Glycyrrhizae Radix et Rhizoma (Gancao) - Hengye Chen; Lixue Ren; Yinan Yang; Wanjun Long; Wei Lan; Jian Yang; Haiyan Fu (Food Chemistry, 2024)

Cofactor engineering in Thermoanaerobacterium aotearoense SCUT27 for maximizing ethanol yield and revealing an enzyme complex with high ferredoxin-NAD+ reductase activity - Kaiqun Dai; Chunyun Qu; Xin Li; Yang Lan; Hongxin Fu; Jufang Wang (Bioresource Technology, 2024)

Identifying modifiable factors and their joint effect on brain health: an exposome-wide association study - Liang-Yu Huang; Yi-Jun Ge; Yan Fu; Yong-Li Zhao; Ya-Nan Ou; Yi Zhang; Ling-Zhi Ma; Shi-Dong Chen; Ze-Xin Guo; Jian-Feng Feng; Wei Cheng; Lan Tan; et al. (GeroScience, 2024)

Glutamine Metabolism Heterogeneity in Glioblastoma Unveils an Innovative Combination Therapy Strategy - Huangde Fu; Shengtian Wu; Hechun Shen; Kai Luo; Zhongxiang Huang; Nankun Lu; Yaolin Li; Qian Lan; Yishun Xian (Journal of Molecular Neuroscience, 2024)

Length-controlled hydrophobic CF3-COF as a highly efficient absorbent coating for dual-mode solid-phase microextraction of sixteen polycyclic aromatic hydrocarbons in water samples - Zirong Lan; Jin Huang; Shanliang Fu; Youwei Chen; Taoyu Meng; Wenli Zhou; Zhou Xu; Maolong Chen; Li Wen; Yunhui Cheng; Li Ding (Science of The Total Environment, 2024)

Insight into energy release characteristics of TiH2 dust explosion through ignition experiments and molecular dynamic simulations - Ting Zhang; Jiefan Zhang; Shuang Geng; Xin Zhang; Runqing Liu; Guoen Fu; Jianfu Xu; Haixia Zhao; Yanhua Lan; Yongan Feng; Weiguo Cao (Process Safety and Environmental Protection, 2024)

Geochemical indications of hydrothermal fluid through sediments within the Geolin Mounds and Mienhua Volcano hydrothermal fields, southernmost Okinawa Trough - Feng-Hsin Hsu; Chih-Chieh Su; Yu-Shih Lin; Hsiao-Fen Lee; Mei-Fei Chu; Tefang Lan; Shein-Fu Wu; Song-Chuen Chen (Deep Sea Research Part I: Oceanographic Research Papers, 2024)

Corrigendum to “Horizontal transfer of antibiotic resistance genes within the bacterial communities in aquacultural environment” [Sci. Total Environ. 820 (2022) 153286] - Songzhe Fu; Qingyao Wang; Rui Wang; Yixiang Zhang; Ruiting Lan; Fenglan He; Qian Yang (Science of The Total Environment, 2024)

Authenticity identification of high – Temperature Daqu Baijiu through multi-channel visual array sensor of organic dyes combined with smart phone App - Yanmei Zhu; Fushuang Xiang; Yuanyuan Su; Xue Jiang; Yipeng Cang; Wanjun Long; Wei Lan; Gaoqiong Deng; Hengye Chen; Yuanbin She; Haiyan Fu (Food Chemistry, 2024)

Mass spectrometry study on SARS-CoV-2 recombinant vaccine with comprehensive separation techniques to characterize complex heterogeneity - Gang Wu; Jialiang Du; Chuanfei Yu; Zhihao Fu; Xiaoxi Zhang; Lan Wang; Junzhi Wang (Analytica Chimica Acta, 2024)

Radiocarbon chronology of sediments with implications for climatic events in Lop Nur, NW China - Yuda Chui; Weijian Zhou; Peng Cheng; Ling Yang; Xingxing Liu; Jianghu Lan; Guoqing Zhao; Shugang Wu; Yunchong Fu; Xiaohu Xiong; Wei Gong (Journal of Asian Earth Sciences, 2024)

Enhanced glutathione production protects against zearalenone-induced oxidative stress and ferroptosis in female reproductive system - Wei Fu; Chao Dai; Zifeng Ma; Qiao Li; Daoliang Lan; Changpo Sun; Xin Wu; Jian Li; Shujin Wang (Food and Chemical Toxicology, 2024)

Maize tassel detection with CA-YOLO for UAV images in complex field environments - Yinjiang Jia; Kang Fu; Hao Lan; Xiru Wang; Zhongbin Su (Computers and Electronics in Agriculture, 2024)

Effects of microbial deodorizer on pig feces fermentation and the underlying deodorizing mechanism - Changning Li; Chen Zhang; Fu Ran; Tuo Yao; Xiaojun Lan; Haiyun Li; Jie Bai; Yang Lei; Ze Zhou; Xiaoning Cui (Waste Management, 2024)

A state-of-the-art review on biomass-derived carbon materials for supercapacitor applications: From precursor selection to design optimization - Hengyuan Hu; Minglei Yan; Jietao Jiang; Ankui Huang; Sicheng Cai; Linxuan Lan; Kewei Ye; Danlei Chen; Kewen Tang; Qin Zuo; Yun Zeng; Wei Tang; et al. (Science of The Total Environment, 2024)

Imidacloprid affects the visual behavior of adult zebrafish (Danio rerio) by mediating the expression of opsin and phototransduction genes and altering the metabolism of neurotransmitters - Ruiqiang Fu; Hongli Liu; Yanning Zhang; Liangang Mao; Lizhen Zhu; Hongyun Jiang; Lan Zhang; Xingang Liu (Science of The Total Environment, 2024)

Thermodynamic investigation of an integrated near-zero CO2 emission power generation system with SOFC, MGT, SCO2BC, and CO2 capture - Fu Wang; Liang Ouyang; Lina Wang; He Miao; Houcheng Zhang; Lan Xia; Lei Wang; Jinliang Yuan (Process Safety and Environmental Protection, 2024)

Deciphering the ore-forming process of Sb-W deposits through scheelite and stibnite trace element geochemistry - Tianxing Wang; Shanling Fu; Neal A. Sullivan; Jiangbo Lan; Luming Wei (Journal of Geochemical Exploration, 2024)

Woody plant cell walls: Fundamentals and utilization - Wei Li; Ying-Chung Jimmy Lin; Ying-Lan Chen; Chenguang Zhou; Shuang Li; Nette De Ridder; Dyoni M. Oliveira; Lanjun Zhang; Baocai Zhang; Jack P. Wang; Changzheng Xu; Xiaokang Fu; et al. (Molecular Plant, 2024)

Highly ion-conducting, robust and environmentally stable poly(vinyl alcohol) eutectic gels designed by natural polyelectrolytes for flexible wearable sensors and supercapacitors - Bai Huang; Wanwan Liu; Yufan Lan; Yuhui Huang; Lihua Fu; Baofeng Lin; Chuanhui Xu (Chemical Engineering Journal, 2024)

Unveiling the role of ABI3 and hub senescence-related genes in macrophage senescence for atherosclerotic plaque progression - Yajuan Fu; Juan Zhang; Qiujun Liu; Lan Yang; Qianqian Wu; Xiaomin Yang; Lexin Wang; Ning Ding; Jiantuan Xiong; Yujing Gao; Shengchao Ma; Yideng Jiang (Inflammation Research, 2024)
Background Atherosclerosis, characterized by abnormal arterial lipid deposition, is an age-dependent inflammatory disease and contributes to elevated morbidity and mortality. Senescent foamy macrophages are considered to be deleterious at all stages of atherosclerosis, while the underlying mechanisms remain largely unknown. In this study, we aimed to explore the senescence-related genes in macrophages diagnosis for atherosclerotic plaque progression. Methods The atherosclerosis-related datasets were retrieved from the Gene Expression Omnibus (GEO) database, and cellular senescence-associated genes were acquired from the CellAge database. R package Limma was used to screen out the differentially expressed senescence-related genes (DE-SRGs), and then three machine learning algorithms were applied to determine the hub DE-SRGs. Next, we established a nomogram model to further confirm the clinical significance of hub DE-SRGs. Finally, we validated the expression of hub SRG ABI3 by Sc-RNA seq analysis and explored the underlying mechanism of ABI3 in THP-1-derived macrophages and mouse atherosclerotic lesions. Results A total of 15 DE-SRGs were identified in macrophage-rich plaques, with five hub DE-SRGs (ABI3, CAV1, NINJ1, Nox4 and YAP1) were further screened using three machine learning algorithms. Subsequently, a nomogram predictive model confirmed the high validity of the five hub DE-SRGs for evaluating atherosclerotic plaque progression. Further, the ABI3 expression was upregulated in macrophages of advanced plaques and senescent THP-1-derived macrophages, which was consistent with the bioinformatics analysis. ABI3 knockdown abolished macrophage senescence, and the NF-κB signaling pathway contributed to ABI3-mediated macrophage senescence. Conclusion We identified five cellular senescence-associated genes for atherogenesis progression and unveiled that ABI3 might promote macrophage senescence via activation of the NF-κB pathway in atherogenesis progression, which proposes new preventive and therapeutic strategies of senolytic agents for atherosclerosis.

Performance evaluation and optimization of hollow fiber membrane contactors for carbon dioxide absorption: A comparative study of ammonia, ethanolamine, and diethanolamine solvents - Jiecheng Xia; Zhiheng Zhang; Lei Wang; Fu Wang; He Miao; Houcheng Zhang; Lan Xia; Jinliang Yuan (Journal of Environmental Chemical Engineering, 2023)

Sources and solubility of aerosol phosphorus at a coastal site in northern China: Coarse versus fine particles and spring versus winter - Shuwei Dong; Huanhuan Zhang; Padmaja Krishnan; Shiguo Jia; Chengpeng Huang; Fu Wang; Lan Luo; Feng Wang; He Meng; Yujiao Zhu; Rui Li; Mingjin Tang (Atmospheric Environment, 2023)

Long period changes of hippocampal diffusion kurtosis imaging and its correlation with cognitive dysfunction after incomplete cerebral ischemia–reperfusion in rats - Lan Fu; Lin-Na Guan; Hongye Zuo (Experimental Brain Research, 2023)

Atmospheric saccharides over the East China Sea: Assessment of the contribution of sea-land emission and the aging of levoglucosan - Mengxin Fu; Hao Li; Lan Wang; Mengke Tian; Xiaofei Qin; Xuan Zou; Cheng Chen; Guochen Wang; Congrui Deng; Kan Huang (Science of The Total Environment, 2023)

Rapid identification of high-temperature Daqu Baijiu with the same aroma type through the excitation emission matrix fluorescence of maillard reaction products - Hengye Chen; Yanmei Zhu; Yufei Xie; Wanjun Long; Wei Lan; Yuanbin She; Haiyan Fu (Food Control, 2023)

Effect of the inoculation of Phanerochaete chrysosporium on nitrogen migration and organic matter conversion during electrolytic manganese residue composting - Xiangyu Peng; Ming Yan; Qingqing Xie; Lan Gao; Xiaojuan Pu; Yukui Fu; Hanwen Liu; Min Cheng; Piao Xu; Danlian Huang; Lin Tang (Bioresource Technology, 2023)

Seasonal differences in continental outflows and marine emissions of organic aerosols in the East China Sea: Insight from the variation of saccharides - Hao Li; Lan Wang; Xiaofei Qin; Guochen Wang; Mengxin Fu; Cheng Chen; Jian Xu; Congrui Deng; Kan Huang (Atmospheric Research, 2023)

Transcriptome profiling reveals multiple regulatory pathways of Tamarix chinensis in response to salt stress - Ruxia Li; Rao Fu; Meng Li; Yanjing Song; Junlin Li; Chuanjie Chen; Yinyu Gu; Xiaoyan Liang; Wenjing Nie; Lan Ma; Xiangyu Wang; Haiyang Zhang; et al. (Plant Cell Reports, 2023)

Maternal Kdm2a-mediated PI3K/Akt signaling and E-cadherin stimulate the morula-to-blastocyst transition revealing crucial roles in early embryonic development - Xianrong Xiong; Manzhen Yang; Zhuo Hai; Xixi Fei; Yanjin Zhu; Bangting Pan; Qinhui Yang; Yumian Xie; Yuying Cheng; Yan Xiong; Daoliang Lan; Wei Fu; et al. (Theriogenology, 2023)

Testis-specific knockout of Kdm2a reveals nonessential roles in male fertility but partially compromises spermatogenesis - Xianrong Xiong; Xiangyue Huang; Yanjin Zhu; Zhuo Hai; Xixi Fei; Bangting Pan; Qinhui Yang; Yan Xiong; Wei Fu; Daoliang Lan; Xiaojian Zhang; Jian Li (Theriogenology, 2023)

Structure-diversified terpenoids from Salvia prattii and their protective activity against alcoholic liver diseases - Xiu-wen Yin; Xiang-xiang Bian; Yan-fang Chen; Ming Zhang; Lan Wu; Fu-cai Ren; Fu-rong Yang; Xiang-dong Pu; Bing-yuan Yang; Chuan-pu Shen (Phytochemistry, 2023)

Effect of co-pyrolysis of sewage sludge with different plastics on the nitrogen, sulfur, and chlorine releasing characteristics and the heavy metals ecological risk of biochar - Jia Shen; Yan Wu; Guoxin Lan; Yaping Xia; Bin Yan; Yurong Li; Yuexin Zhang; Yue Yu; Chuan Fu; Anji Xu; Jie Zhou; Ailing Zhu; et al. (Journal of Environmental Chemical Engineering, 2023)

Advances in nanocomposite organic coatings for hydraulic fracturing proppants - Juan Du; Qisheng Huang; Pingli Liu; Yangyang Fu; Xitang Lan; Xiang Chen; Jinming Liu; Xiao Lu (Gas Science and Engineering, 2023)

Temporal and spatial distributions, source identification, and health risk assessment of polycyclic aromatic hydrocarbons in PM2.5 from 2016 to 2021 in Shenzhen, China - Jinfeng Fu; Jiajia Ji; Lan Luo; Xiaoheng Li; Xiaoxin Zhuang; Ying Ma; Qilan Wen; Yue Zhu; Jiaojiao Ma; Jiayin Huang; Duo Zhang; Shaoyou Lu (Environmental Science and Pollution Research, 2023)

Molecular cloning and characterization of STC1 gene and its functional analyses in yak (Bos grunniens) cumulus granulosa cells - Xue Yang; Jun Ma; Luoyu Mo; Yan Xiong; Xianrong Xiong; Daoliang Lan; Wei Fu; Shi Yin (Theriogenology, 2023)

Characterization of the key aroma compounds in soy sauce by gas chromatography-mass spectrometry-olfactometry, headspace-gas chromatography-ion mobility spectrometry, odor activity value, and aroma recombination and omission analysis - Peipei Wang; Qixin Kan; Lixin Yang; Weitao Huang; Linfeng Wen; Jiangyan Fu; Zhan Liu; Yaqi Lan; Qingrong Huang; Chi-Tang Ho; Yong Cao (Food Chemistry, 2023)

Maternal di-(2-ethylhexyl) phthalate exposure elicits offspring IFN-λ upregulation: Insights from birth cohort, murine model, and in vitro mechanistic analysis - Fu-Chen Kuo; Mei-Lan Tsai; Shin-Ting Wu; Sih-Syuan Li; Chia-Fang Wu; Shu-Lin Wang; Michael W.Y. Chan; Jau-Ling Suen; Ming-Tsang Wu; Chih-Hsing Hung (Food and Chemical Toxicology, 2023)

Systemic lupus erythematosus with high disease activity identification based on machine learning - Da-Cheng Wang; Wang-Dong Xu; Zhen Qin; Lu Fu; You-Yu Lan; Xiao-Yan Liu; An-Fang Huang (Inflammation Research, 2023)

Metagenome-based analysis of carbon-fixing microorganisms and their carbon-fixing pathways in deep-sea sediments of the southwestern Indian Ocean - Xiao-Lan Yue; Lin Xu; Li Cui; Ge-Yi Fu; Xue-Wei Xu (Marine Genomics, 2023)

Effectively removing gaseous polycyclic aromatic hydrocarbons (PAHs) by willow catkins: Do you still dislike the catkins floating? - Peng-Tuan Hu; Dong-Hai Liu; Zhi-Guo Cao; Hong Wei; Fu-Jie Zhu; Wan-Li Ma; Zi-Feng Zhang; Li-Yan Liu; Jing-Lan Feng; Yong-Feng Li; Yu-Fei Li; Yi-Fan Li (Journal of Hazardous Materials, 2023)

Heterogeneous reaction of NO2 with feldspar, three clay minerals and Arizona Test Dust - Mingjin Tang; Xiaohong Jia; Lanxiadi Chen; Wenjun Gu; Chengpeng Huang; Fu Wang; Lan Luo; Hongli Wang; Xinming Wang; Chao Peng (Journal of Environmental Sciences, 2023)

Urinary Amino-PAHs in relation to diesel engine emissions and urinary mutagenicity - Junfeng (Jim) Zhang; Yuxin Zheng; Roel Vermeulen; Xing (Lucy) Liu; Yufei Dai; Wei Hu; Linchen He; Yan Lin; Dianzhi Ren; Huawei Duan; Yong Niu; Jun Xu; et al. (International Journal of Hygiene and Environmental Health, 2023)

Simultaneous removal of antibiotic-resistant Escherichia coli and its resistance genes by dielectric barrier discharge plasma - Shuheng Hu; Yuhang Fu; Muen Xue; Yan Lan; Wenhao Xi; Zimu Xu; Wei Han; Danzhou Wu; Cheng Cheng (Environmental Research, 2023)

TiO2 nanoparticles affect spermatogenesis and adhesion junctions via the ROS-mediated mTOR signalling pathway in Eriocheir sinensis testes - Lan-Min Wang; Ke Jia; Zhen-Fang Li; Hong-Yu Qi; Ding-Xi Liu; Ya-Jing Liang; Shuang-Li Hao; Fu-Qing Tan; Wan-Xi Yang (Environmental Pollution, 2023)

Spatio-temporal variation and hazard assessment of potentially toxic metal element contamination in sediments and water before and after a water-level fluctuation cycle in the Three Gorges Reservoir, Wanzhou, China - Chang Liu; Qiaojuan Lan; Bin Yan; Jueqiao Wang; Huan Wang; Yan Wu; Chuan Fu; Yinhai Zhong; Chao Li; Shenglei Li (Environmental Monitoring and Assessment, 2023)

The dynamics of the equatorial Atlantic upwelling seasonal cycle under global warming and its potential impact on Pacific ENSO - Li-Chiao Wang; Thi Lan Dao; Yong-Fu Lin; Jia-Yuh Yu (Climate Dynamics, 2023)

Developmental defects and potential mechanisms in F1 generation of parents exposed to difenoconazole at different life stages of zebrafish (Danio rerio) - Yiming Chang; Huimin Fu; Haitao Yu; Liangang Mao; Lan Zhang; Yanning Zhang; Lizhen Zhu; Jin Yang; Xingang Liu; Hongyun Jiang (Science of The Total Environment, 2023)

The PIWI-specific insertion module helps load longer piRNAs for translational activation essential for male fertility - Xin Wang; Di-Hang Lin; Yue Yan; An-Hui Wang; Jiaoyang Liao; Qian Meng; Wen-Qing Yang; Heng Zuo; Min-Min Hua; Fengjuan Zhang; Hongwen Zhu; Hu Zhou; et al. (Science China Life Sciences, 2023)

Correction to: Decreased sustained attention, processing speed and verbal learning memory in patients with insomnia in Chinese young and middle-aged adults: a cross-sectional study - Xie Chen; Cai-Lan Hou; Shi-Bin Wang; Zhuo-Hui Huang; Ying-Hua Huang; Xue-Li Li; Fu-Jun Jia (Sleep and Biological Rhythms, 2023)

Isolation and structure determination of superbcyclin A, a cyclic nonapeptide from Dianthus superbus - Qing Zhang; Jing-Hui Yang; Yu-Lan Du; Xu-Yang Fu; Wu-Yang Liu; Yi-Qin Zeng; Shu-Hui Liu; Jun-Mian Tian; Jin-Ming Gao (Phytochemistry Letters, 2023)

Effects of pile fermentation on the physicochemical, functional, and biological properties of tea polysaccharides - Qian Li; Lu Liu; Jiahan Zhang; Mingyu Dong; Lan Wang; David Julian McClements; Yinxin Fu; Lingyu Han; Peiyi Shen; Xiaoqiang Chen (Food Chemistry, 2023)

Sedimentary organic matter molecular composition reveals the eutrophication of the past 500 years in Lake Daihai, Inner Mongolia - Chukun Hu; Hai Xu; Siwei Shi; Jianghu Lan; Kang'en Zhou; Jin Zhang; Yunping Song; Jing Wang; Pingqing Fu (Environmental Research, 2023)

Overlooked impacts of natural organic matter conversion in a Fe(II)-induced peroxymonosulfate activation system for river water remediation - Lan Liang; Guanyi Chen; Jianhui Zhao; Penghui Shao; Ning Li; Mengting He; Qinglong Fu; Beibei Yan; Li-an Hou (Science of The Total Environment, 2023)

Mechanisms of acidic electrolyzed water killing bacteria - Fan Wang; Yan-Ning Lin; Yu Xu; Yong-Bing Ba; Zhao-Huan Zhang; Li Zhao; Wing Lam; Fu-Lan Guan; Yong Zhao; Chang-Hua Xu (Food Control, 2023)

Integrate transcriptomic and metabolomic analysis reveals the underlying mechanisms of behavioral disorders in zebrafish (Danio rerio) induced by imidacloprid - Hongli Liu; Ruiqiang Fu; Yanning Zhang; Liangang Mao; Lizhen Zhu; Lan Zhang; Xingang Liu; Hongyun Jiang (Science of The Total Environment, 2023)

Combined ecotoxicological effects of different-sized polyethylene microplastics and imidacloprid on the earthworms (Eisenia fetida) - Huimin Fu; Lizhen Zhu; Liangang Mao; Lan Zhang; Yanning Zhang; Yiming Chang; Xingang Liu; Hongyun Jiang (Science of The Total Environment, 2023)

Thermal decomposition, flame propagation, and combustion reactions behaviours of stearic acid by experiments and molecular dynamic simulation - Wenjuan Li; Xin Zhang; Runqing Liu; Siyu Xu; Sen Xu; Yanhua Lan; Yizheng Fu; Yun Zhang; Yongan Feng; Weiguo Cao (Chemical Engineering Journal, 2023)

Comparison of the chronic and multigenerational toxicity of racemic glufosinate and -glufosinate to Caenorhabditis elegans at environmental concentrations - Xu Zhao; Kan Fu; Kai-ping Xiang; Lan-ying Wang; Yun-fei Zhang; Yan-ping Luo (Chemosphere, 2023)

24-Epibrassinolide Enhances Resistance Against Colletotrichum fructicola by Promoting Lignin Biosynthesis in Camellia sinensis L. - Lan Zhang; Zheng Zhang; Golam Jalal Ahammed; Xiaorong Wang; Huihan Fang; Peng Yan; Li-Ping Zhang; Shibei Ge; Jianyu Fu; Wen-Yan Han; Xin Li (Journal of Plant Growth Regulation, 2023)

Mesenchymal stem cells suppressed skin and lung inflammation and fibrosis in topoisomerase I-induced systemic sclerosis associated with lung disease mouse model - Nithya Ganesan; Yu-Di Chang; Shih-Chieh Hung; Joung-Liang Lan; Jiunn-Wang Liao; Shih Tsung Fu; Chen-Chen Lee (Cell and Tissue Research, 2023)

Risk assessment of metal(loid)s in tea from seven producing provinces in China - Xiaoling Wu; Duo Zhang; Fu Wang; Lan Luo; Yining Chen; Shaoyou Lu (Science of The Total Environment, 2023)

Efficient enrichment of iodine by supported ionic liquid with three effective adsorption sites: Heteroatoms, fused aromatic rings and ionic bond - Yu-Qin Xiang; Yuan-Hao Wang; Hao Chen; Jie Fu; Qiu-Hong Zhu; Xiao-Lan Yang; Xin-Hong Xu; Song Qin; Ling He; Guo-Hong Tao (Chemical Engineering Journal, 2023)

Lanthanoid hydrogen-bonded organic frameworks: Enhancement of luminescence by the coordination-promoted antenna effect and applications in heavy-metal ion sensing and sterilization - Yun-Lan Li; Hai-Ling Wang; Zhi-Chuan Chen; Zhong-Hong Zhu; Yan-Cheng Liu; Rui-Yun Yang; Fu-Pei Liang; Hua-Hong Zou (Chemical Engineering Journal, 2023)

The diversity and structure of diazotrophic communities in the rhizosphere of coastal saline plants is mainly affected by soil physicochemical factors but not host plant species - Yanjing Song; Lan Ma; Haiyang Zhang; Rao Fu; Xiaoyan Liang; Junlin Li; Jiajia Li; Meng Li; Yan Shan; Jieshan Cheng; Xiangyu Wang; Hongxia Zhang (Frontiers in Marine Science, 2022)
The diversity and community structure of rhizospheric microbes are largely affected by soil physicochemical properties and plant species. In this work, high throughput sequencing and quantitative real-time PCR targeting nifH gene were used to assess the abundance and diversity of diazotrophic community in the coastal saline soils of Yellow River Delta (YRD). We demonstrated that the copy number of nifH gene encoding the Fe protein subunit of the nitrogenase in the nitrogen fixation process was significantly affected by soil physiochemical factors, and the abundance of diazotrophs in the rhizospheric soil samples collected from different locations was positively related with soil physicochemical properties. Soil salinity ( P =0.003) and moisture ( P =0.003) were significantly co-varied with the OTU-based community composition of diazotrophs. Taxonomic analysis showed that most diazotrophs belonged to the Alphaproteobacteria , Gammaproteobacteria and Deltaproteobacteria . Linear discriminant analysis (LDA) effect size (LEfSe) and canonical correspondence analysis (CCA) showed that diazotrophic community structure significantly varied with soil salinity, moisture, pH and total nitrogen, carbon, sulphur and nitrite (NO 2 – N) content. Our findings provide direct evidence toward the understanding of different effects of soil physicochemical properties and host plant traits such as halophytes types, life span and cotyledon type, on the community composition of diazotrophic populations in the rhizosphere of plants grown in coastal saline soils.

Cloning of Two HSP Genes of Eriocheir hepuensis and Their Expression under Vibrio parahaemolyticus Stress - Qianni Fu; Jinxia Liu; Tianjiao Ren; Zining Zhang; Zihang Ma; Zhenyu Lan; Yitao Duan; Ziwei Liang; Boyu Chen; Yan Zhang; Peng Zhu; Yongyan Liao (Fishes, 2022)
Heat shock proteins (HSPs) are molecular chaperone proteins that can help maintain cellular protein homeostasis, assist in correcting the folding of cellular proteins, and protect organisms from stress when the body is under stress conditions such as temperature changes or bacterial infections. In this study, the HSP10 and HSP40 genes of Eriocheir hepuensis were cloned and named Eh-HSP10 and Eh-HSP40. The results show that the coding sequence length of the HSP10 and HSP40 genes of E. hepuensis was 309 bp and 1191 bp, encoding 102 and 396 amino acids, respectively. The results of protein domain prediction show that Eh-HSP10 has a Cpn10 domain. The Eh-HSP40 protein contains a DnaJ domain, which is characteristic of the HSP40 gene family. The results of qRT-PCR show that the Eh-HSP10 and Eh-HSP40 genes were expressed in different normal tissues, with the highest expression in the heart. Under Vibrio parahaemolyticus stress, the Eh-HSP10 genes peaked at 6 h, and the Eh-HSP40 peaked at 9 h in the hepatopancreas. In the gill, Eh-HSP10 showed a double peak at 24 and 48 h, and the expression of Eh-HSP40 was time-dependent. In the heart, the expression of Eh-HSP10 increased first and then decreased, whereas Eh-HSP40 peaked at 48 h. The results indicate that the Eh-HSP10 and Eh-HSP40 proteins may play a role in protecting E. hepuensis under V. parahaemolyticus infection and that they may be involved in the innate immune response of E. hepuensis against bacteria.

Evolution mechanism and deformation stability analysis of rock slope block toppling for early warnings - Jian-qiao Mu; Tian-tao Li; Xiang-jun Pei; Run-qiu Huang; Fu-an Lan; Xue-qing Zou (Natural Hazards, 2022)

Proteomic analysis and identification reveal the anti-inflammatory mechanism of clofazimine on lipopolysaccharide-induced acute lung injury in mice - Bo Yang; Zhan Gao; Qi-Shuang Li; Xiang-Ye Zhang; Lan Song; Yi-Ni Wang; Xin-Yue Wang; Lin-Lin Ji; Hong-Liang Xu; Hui Xie; Fu-Kai Feng; Xiao-Ping Li; et al. (Inflammation Research, 2022)

mTORC1/C2 regulate spermatogenesis in Eriocheir sinensis via alterations in the actin filament network and cell junctions - Zhen-Fang Li; Shuang-Li Hao; Lan-Min Wang; Hong-Yu Qi; Jia-Ming Wang; Fu-Qing Tan; Wan-Xi Yang (Cell and Tissue Research, 2022)

Monoterpenoid indole alkaloids with potential neuroprotective activities from the stems and leaves of Melodinus cochinchinensis - Yu-Jie Li; Juan Li; Lan Xie; Jun-Yu Zhou; Qiu-Xuan Li; Rui-Yuan Yang; Yan-Ping Liu; Yan-Hui Fu (Natural Product Research, 2022)

IL-38, a potential therapeutic agent for lupus, inhibits lupus progression - Wang-Dong Xu; Lin-Chong Su; Lu Fu; You-Yu Lan; Xiao-Yan Liu; Qi Huang; Qian Wu; Jie Zhou; An-Fang Huang (Inflammation Research, 2022)

Ectomycorrhizal synthesis between two Tuber species and six tree species: are different host-fungus combinations having dissimilar impacts on host plant growth? - Lan-Lan Huang; Yan-Liang Wang; Alexis Guerin-Laguette; Ran Wang; Peng Zhang; Yong-Mei Li; Fu-Qiang Yu (Mycorrhiza, 2022)

Cadinane-type sesquiterpenes with potential anti-inflammatory and anti-HIV activities from the stems and leaves of Mappianthus iodoides - Yan-Ping Liu; Xiao-Mei Yu; Ze-Hua Qiao; Bo Jiang; Lan Xie; Hao-Xuan Tang; Xiao Liang; Yan-Hui Fu (Natural Product Research, 2022)

Alteromonas oceanisediminis sp. nov., isolated from deep-sea sediment - Xiao-Yu Zhang; Zhen Wang; Jun-Hui Cheng; Hui-Hui Fu; Yu-Zhong Zhang; Xiu-Lan Chen; Xi-Ying Zhang; Xiao-Yan Song; Yu-Qiang Zhang; Fei Xu (Archives of Microbiology, 2022)

Black-Box Modelling and Prediction of Deep-Sea Landing Vehicles Based on Optimised Support Vector Regression - Hongming Sun; Wei Guo; Yanjun Lan; Zhenzhuo Wei; Sen Gao; Yu Sun; Yifan Fu (Journal of Marine Science and Engineering, 2022)
Due to the nonlinearity of the deep-seafloor and complexity of the hydrodynamic force of novel structure platforms, realising an accurate motion mechanism modelling of a deep-sea landing vehicle (DSLV) is difficult. The support vector regression (SVR) model optimised through particle swarm optimisation (PSO) was used to complete the black-box motion modelling and vehicle prediction. In this study, first, the prototype and system composition of the DSLV were proposed, and subsequently, the high-dimensional nonlinear mapping relationship between the motion state and the driving forces was constructed using the SVR of radial basis function. The high-precision model parameter combination was obtained using PSO, and, subsequently, the black-box modelling and prediction of the vehicle were realised. Finally, the effectiveness of the method was verified through multi-body dynamics simulation and scaled test prototype data. The experimental results confirmed that the proposed PSO–SVR model could establish an accurate motion model of the vehicle, and provided a high-precision motion state prediction. Furthermore, with less calculation, the proposed method can reliably apply the model prediction results to the intelligent behaviour control and planning of the vehicle, accelerate the development progress of the prototype, and minimise the economic cost of the research and development process.

Involvement of Opioid Peptides in the Analgesic Effect of Spinal Cord Stimulation in a Rat Model of Neuropathic Pain - Fu-Jun Zhai; Song-Ping Han; Tian-Jia Song; Ran Huo; Xing-Yu Lan; Rong Zhang; Ji-Sheng Han (Neuroscience Bulletin, 2022)

Effects of Artemisia ordosica on fine-scale spatial distribution of soil C, N and P and physical–chemical properties in the Mu Us Desert, China - Zhilong Lan; Shaolei Zhang; Liangchen Xie; Xiong Li; Tanveer Ali Sial; Abdu Ghaffar Shar; Jinglong Fan; Jianguo Zhang; Qiang Dong; Guangjun Fu (Journal of Soils and Sediments, 2022)

N-acetylcysteine alleviates pulmonary inflammatory response during benzo[a]pyrene-evoked acute lung injury - Hui Zhao; Lin Fu; Hui-Xian Xiang; Ying Xiang; Meng-Die Li; Bian-Bian Lv; Zhu-Xia Tan; Lan Gao; Cheng Zhang; De-Xiang Xu (Environmental Science and Pollution Research, 2022)

Biogeography of culturable marine bacteria from both poles reveals that ‘everything is not everywhere’ at the genomic level - Qi‐Long Qin; Zhi‐Bin Wang; Qian‐Qian Cha; Sha‐Sha Liu; Xue‐Bing Ren; Hui‐Hui Fu; Mei‐Ling Sun; Dian‐Li Zhao; Andrew McMinn; Yin Chen; Xiu‐Lan Chen; Yu‐Zhong Zhang; et al. (Environmental Microbiology, 2022)
Summary Based on 16S rRNA gene analyses, the same bacterial operational taxonomic units (OTUs) are common to both the Arctic and Antarctic oceans, supporting the concept ‘everything is everywhere’. However, whether the same OTUs from both poles have identical genomes, i.e. whether ‘everything is still everywhere’ at the genomic level has not yet been examined systematically. Here, we isolated, sequenced and compared the genomes of 45 culturable marine bacteria belonging to three genera of Salinibacterium , Psychrobacter and Pseudoalteromonas from both polar oceans. The bacterial strains with identical 16S rRNA genes were common to both poles in every genus, and four identical genomes were detected in the genus Salinibacterium from the Arctic region. However, no identical genomes were observed from opposite poles in this study. Our data, therefore, suggest that ‘everything is not everywhere’ at the genomic level. The divergence time between bacteria is hypothesized to exert a strong impact on the bacterial biogeography at the genomic level. The geographical isolation between poles was observed for recently diverged, highly similar genomes, but not for moderately similar genomes. This study thus improves our understanding of the factors affecting the genomic‐level biogeography of marine microorganisms isolated from distant locations.

Responses of leaf litter decomposability to nitrogen and phosphorus additions are associated with cell wall carbohydrate composition in a subtropical plantation - Xiang-Min Fang; Xiu-Lan Zhang; Ying-Ying Zong; Wen-Qing Li; Jian-Jun Li; Li-Ping Guo; Huimin Wang; Fu-Sheng Chen (Plant and Soil, 2021)

An efficient genetic manipulation protocol for dark septate endophyte Falciphora oryzae - Zhen-Zhu Su; Meng-Di Dai; Jia-Nan Zhu; Yu-Lan Zeng; Xuan-Jun Lu; Xiao-Hong Liu; Fu-Cheng Lin (Biotechnology Letters, 2021)

Effects of Mn2+ on neutral lipid content, C4 pathway, and related gene expression in Phaeodactylum tricornutum - Rong-Shi Chen; Li Zhang; Feng-Juan Wei; Lan-Ying Yuan; Pu Zhao; He-Yu Wang; Yi-Fu Gong (Journal of Applied Phycology, 2021)

Marinifaba aquimaris gen. nov., sp. nov., a novel chitin‐degrading gammaproteobacterium in the family Alteromonadaceae isolated from seawater of the Mariana Trench - Xin Sui; Xiao-yan He; Ning-hua Liu; Yan-ru Dang; Qian-qian Cha; Mei-ling Sun; Chun-yang Li; Hui-hui Fu; Xiao-yan Song; Qi-long Qin; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Long-Term Variability of Piscivorous Fish in China Seas Under Climate Change With Implication for Fisheries Management - Dan Liu; Yongjun Tian; Shuyang Ma; Jianchao Li; Peng Sun; Zhenjiang Ye; Caihong Fu; Kuowei Lan; Shijie Zhou (Frontiers in Marine Science, 2021)
Due to persistent fishing expansion in the China Seas over the past six decades, fisheries resources have been over-exploited; as a result, exploited fish have become smaller in size and younger in age. Marine piscivorous fish constituted a large portion of Chinese fisheries catch, long-term variability of which has rarely been investigated despite intense fishing pressure and climate change. In this study, we attempt to identify their responses to climate change and fishing activities and to provide scientific basis for sustainable exploitation of these resources. Seven taxa from pelagic to demersal species inhabiting either cold-water or warm-water were selected to represent the piscivorous fish assemblage in the China Seas. Total catch of these piscivorous fish in the China Seas increased during the early 1990s, stabilizing around 1.2 million tons after 1997. Principal component analysis (PCA) showed evident interannual-decadal variabilities in the catch of these fish with step changes around 1985/86 and 1997/98. Individual taxa, however, showed different trends in catches with sharks, rays, and lizardfishes manifesting downward trends while Pacific cod, eels, and hairtail increasing. Common dolphinfish and Japanese-Spanish mackerel increased largely in the 1990s but declined slightly during the 2000s. Although there were temporal overlaps between climate change and fishing variabilities, results of gradient forest analyses indicated that fishing effort imposed the most important influence on piscivorous fish. And among all climate variables explored in this study, sea surface temperature (SST) especially that of the East China Sea, had greatest impacts on variations in piscivorous fish catch, which may have been gradually exacerbated by the continued high fishing intensity. In addition, significant changes were identified in the life history traits in the species we evaluated, such as reduced average body sizes and truncated age compositions, strongly indicating the effect of fishing. We therefore advocate precautionary fishery practices under climate change.

A survey of chloramphenicol residues in aquatic products of Shenzhen, South China - Lan Luo; Shaoyou Lu; Chengpeng Huang; Fu Wang; Yan Ren; He Cao; Qihui Lin; Zhiqiang Tan; Xiaodong Wen (Food Additives & Contaminants: Part A, 2021)

Sleep Characteristics and Cerebrospinal Fluid Progranulin in Older Adults: The CABLE Study - Meng Wang; Fu-Rong Sun; Yan-Lin Bi; Ya-Hui Ma; Jian-Jun Yin; Xue-Ning Shen; Xiao-Tong Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2021)

Tritonibacter aquimaris sp. nov. and Tritonibacter litoralis sp. nov., two novel members of the Roseobacter group isolated from coastal seawater - Na Li; Xiao-yan He; Ning-hua Liu; Tie-ji Gu; Jian Li; Yu-hui Geng; Shan Zhang; Peng Wang; Hui-hui Fu; Mei Shi; Xiu-lan Chen; Yu-zhong Zhang; et al. (Antonie van Leeuwenhoek, 2021)

Cryostructures and ground ice content in ice-rich permafrost area of the Qinghai-Tibet Plateau with Computed Tomography Scanning - Xing-wen Fan; Zhan-ju Lin; Ze-yong Gao; Xiang-lian Meng; Fu-jun Niu; Jing Luo; Guo-an Yin; Fu-jun Zhou; Ai-yu Lan (Journal of Mountain Science, 2021)

Litter addition and understory removal influenced soil organic carbon quality and mineral nitrogen supply in a subtropical plantation forest - Xiang-Min Fang; G. Geoff Wang; Zhi-Jun Xu; Ying-Ying Zong; Xiu-Lan Zhang; Jian-Jun Li; Huimin Wang; Fu-Sheng Chen (Plant and Soil, 2021)

Response of palladium in receiving water bodies to rainfall-runoff - Fangfang Ding; Yuyan Liu; Zucheng Wang; Caiye Ji; Dan Wu; Lin Wang; Bo Fu; Lan Zhang; Haofeng Liu (Environmental Science and Pollution Research, 2021)

Experimental evidence for long‐term coexistence of copiotrophic and oligotrophic bacteria in pelagic surface seawater - Yi Li; Zhi‐Bin Wang; Xi‐Ying Zhang; Yan‐Ru Dang; Lin‐Lin Sun; Wei‐Peng Zhang; Hui‐Hui Fu; Gui‐Peng Yang; Min Wang; Andrew McMinn; Xiu‐Lan Chen; Yin Chen; et al. (Environmental Microbiology, 2021)
Summary Most marine copiotrophic bacteria can produce extracellular enzymes to degrade biopolymers into bio‐available smaller solutes, while oligotrophic bacteria usually cannot. Bacterial extracellular enzymes and enzymatic products can be a common resource that could be utilized by both copiotrophs and oligotrophs; when present, oligotrophs may outcompete the enzyme‐producing copiotrophs. However, copiotrophs and oligotrophs consistently coexist in the ocean. How they maintain coexistence has still not been experimentally studied. In this study, the interaction and coexistence of a copiotroph and an oligotroph, isolated from the same surface seawater sample and utilizing the same proteinaceous substrate, were experimentally investigated. The copiotroph could secrete extracellular proteases to degrade and then utilize the proteinaceous substrate. The oligotroph was unable to utilize the proteinaceous substrate by itself, but could grow by using the hydrolysate amino acids. The copiotroph outcompeted the oligotroph by adsorbing the amino acids quickly and having a higher growth rate in the rich medium. The oligotroph survived by adapting to low concentration of nutrients. The copiotroph and oligotroph were able to maintain long‐term (up to 142 days) coexistence in the laboratory. This study indicates that differences in the utilization of different concentrations of nutrients can drive the coexistence of marine copiotrophs and oligotrophs.

Correction to: Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Chang-Qi Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Involvement of proBDNF in Monocytes/Macrophages with Gastrointestinal Disorders in Depressive Mice - Yun-Qing Yu; Yan-Ling Zhang; Zhe Wang; Yu Liu; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2020)

Characterization of Tuber indicum (Pezizales, Tuberaceae) mycorrhizae synthesized with four host trees exotic to China - Lan-Lan Huang; Alexis Guerin-Laguette; Ran Wang; Fu-Qiang Yu (Symbiosis, 2020)

Discrimination of geographical origin of camellia seed oils using electronic nose characteristics and chemometrics - Qi Peng; Qinxia Xu; Bealu Girma Dula; Jiazheng Wang; Jianwei Fu; Lan Wang; Bin Qian; Jiandi Zhou; Jianjiang Wu; Jiali Wang; Yinjun Ding (Journal of Consumer Protection and Food Safety, 2020)

KIF3A regulates the Wnt/β-catenin pathway via transporting β-catenin during spermatogenesis in Eriocheir sinensis - Ya-Jing Liang; Jia-Hao Ni; Lan-Min Wang; Fu-Qing Tan; Wan-Xi Yang (Cell and Tissue Research, 2020)

Temporal variation and distribution of size fractionated: platinum group elements and heavy metals in total suspended particulate - Yuyan Liu; Bo Fu; Cheng Liu; Yaxing Shen; Haofeng Liu; Zhang Lan (Meteorology and Atmospheric Physics, 2020)

Fishmeal level affects growth performance of Macrobrachium nipponense via regulating protein and lipid metabolism - Qun-Lan Zhou; Su-Fei Jiang; Yi-Wei Xiong; Bo Liu; Cunxin Sun; Zhenting Jiang; Hongtuo Fu (Aquaculture International, 2020)

Decreased sustained attention, processing speed and verbal learning memory in patients with insomnia in Chinese young and middle-aged adults: a cross-sectional study - Xie Chen; Cai-Lan Hou; Shi-Bin Wang; Zhuo-Hui Huang; Ying-Hua Huang; Xue-Li Li; Fu-Jun Jia (Sleep and Biological Rhythms, 2020)

Influence of Sediment Characteristics on Heavy Metal Fraction Distribution in the Water-Level Fluctuation Zone of the Three Gorges Reservoir Area, China - Chuan Fu; Qiaojuan Lan; Yan Wu; Bin Yan; Wei Ping; Lianqi Huang; Binrong Yang (Water, Air, & Soil Pollution, 2020)

Serum Uric Acid Levels and Risk of Intracranial Atherosclerotic Stenosis: A Cross-Sectional Study - Lin Li; Jun-Xia Zhu; Xiao-He Hou; Ya-Hui Ma; Wei Xu; Chen-Chen Tan; Fu-Rong Sun; Hong-Qi Li; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Environmental policy, tax, and the target of sustainable development - Jie Yang; Mei-Lan Chen; Chung-Yuan Fu; Xi-Ding Chen (Environmental Science and Pollution Research, 2020)

Effect of Freezing–Thawing Cycle on Soil Active Organic Carbon Fractions and Enzyme Activities in the Wetland of Sanjiang Plain, Northeast China - Fu Li; Shuying Zang; Yingnan Liu; Lan Li; Hongwei Ni (Wetlands, 2020)

Elevated Hs-CRP Levels Are Associated with Higher Risk of Intracranial Arterial Stenosis - Bing-Jie Su; Yi Dong; Chen-Chen Tan; Xiao-He Hou; Wei Xu; Fu-Rong Sun; Mei Cui; Qiang Dong; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2020)

Isolation, identification and character analysis of Streptococcus dysgalactiae from Megalobrama terminalis - Fei Zhao; Shan He; Ai‐ping Tan; Xue‐zhong Guo; Lan Jiang; Cui Liu‐Fu; Yu‐ting Deng; Rui‐quan Zhang (Journal of Fish Diseases, 2020)
Pure bacterial cultures were isolated from different tissues of moribund Megalobrama terminalis from a high mortality event that occurred at a farm in Foshan, China. Two isolates (F2 and F3) were identified as Streptococcus dysgalactiae subsp. dysgalactiae based on morphological and biochemical detection as well as molecular analysis. In brain heart infusion broth, the best growth conditions of isolate F3 were 35ºC, salinity 5‰ and pH 7. Furthermore, infection with isolate F3 (1.2 × 10 6 CFU/fish) led to the death of M. terminalis and zebrafish ( Danio rerio ). However, isolate F3 had no obvious pathogenicity to tilapia (GIFT, Oreochromis niloticus ). When the water temperature was 29ºC, the corresponding mortality rates for zebrafish infected by isolate F3 were higher than those at 23ºC. Culture for 24 and 72 hr with isolate F3 resulted in the same mortality rates for zebrafish. The antimicrobial susceptibility assay revealed that isolate F3 was susceptible to ampicillin, florfenicol and several other antibiotics but resistant to nalidixic acid, streptomycin, sulfamethoxazole/trimethoprim, neomycin and amikacin. To our knowledge, this is the first report that S. dysgalactiae infected the subtropical freshwater fish M. terminalis , which indicates that this bacterium is a potential threat to subtropical freshwater fish.

Toxicity and metabolism of 3-bromopyruvate in Caenorhabditis elegans - Qiao-ling Gu; Yan Zhang; Xi-mei Fu; Zhao-lian Lu; Yao Yu; Gen Chen; Rong Ma; Wei Kou; Yong-mei Lan (Journal of Zhejiang University-SCIENCE B, 2020)

Application of Cas12a and nCas9-activation-induced cytidine deaminase for genome editing and as a non-sexual strategy to generate homozygous/multiplex edited plants in the allotetraploid genome of tobacco - Chen-Tran Hsu; Yu-Jung Cheng; Yu-Hsua Yuan; Wei-Fon Hung; Qiao-Wei Cheng; Fu-Hui Wu; Lan-Ying Lee; Stanton B. Gelvin; Choun-Sea Lin (Plant Molecular Biology, 2019)

The European delicacy Tuber melanosporum forms mycorrhizae with some indigenous Chinese Quercus species and promotes growth of the oak seedlings - Ran Wang; Alexis Guerin-Laguette; Ruth Butler; Lan-Lan Huang; Fu-Qiang Yu (Mycorrhiza, 2019)

Two-factor ANOVA of SSH and RNA-seq analysis reveal development-associated Pi-starvation genes in oilseed rape - Zhong-Wei Zhang; Ling-Yang Feng; Jian-Hui Wang; Yu-Fan Fu; Xin Cai; Chang-Quan Wang; Jun-Bo Du; Ming Yuan; Yang-Er Chen; Pei-Zhou Xu; Ting Lan; Guang-Deng Chen; et al. (Planta, 2019)

Upregulation of proBDNF in the Mesenteric Lymph Nodes in Septic Mice - Zhe Wang; Jia-Li Wu; Feng Zhong; Yu Liu; Yun-Qing Yu; Jing-Jing Sun; Shuang Wang; Hui Li; Xin-Fu Zhou; Zhao-Lan Hu; Ru-Ping Dai (Neurotoxicity Research, 2019)

Erratum to: Rapid generation of genetic diversity by multiplex CRISPR/Cas9 genome editing in rice - Lan Shen; Yufeng Hua; Yaping Fu; Jian Li; Qing Liu; Xiaozhen Jiao; Gaowei Xin; Junjie Wang; Xingchun Wang; Changjie Yan; Kejian Wang (Science China Life Sciences, 2019)

Development of Twin Temperature Compensation and High-Level Biaxial Pressurization Calibration Techniques for CSIRO In-Situ Stress Measurement in Depth - Yuan Li; Shuangshuang Fu; Lan Qiao; Zibin Liu; Yihai Zhang (Rock Mechanics and Rock Engineering, 2019)

Microsatellite records for volume 11, issue 1 - Da-Qing Chen; Zaijie Dong; Min Fang; Jianjun Fu; Xiang-Yang Jia; Bingjie Jiang; Jingmiao Li; Qingqing Li; Suhui Liao; Ping Liu; Yulin Liu; Guocheng Shu; et al. (Conservation Genetics Resources, 2019)

A Genome-Wide Association Study of α-Synuclein Levels in Cerebrospinal Fluid - Xiao-ling Zhong; Jie-Qiong Li; Li Sun; Ya-Qing Li; Hui-Fu Wang; Xi-Peng Cao; Chen-Chen Tan; Ling Wang; Lan Tan; Jin-Tai Yu (Neurotoxicity Research, 2019)

Small-world indices via network efficiency for brain networks from diffusion MRI - Lan Lin; Zhenrong Fu; Cong Jin; Miao Tian; Shuicai Wu (Experimental Brain Research, 2018)

Transcranial Ultrasound Stimulation Improves Long-Term Functional Outcomes and Protects Against Brain Damage in Traumatic Brain Injury - Szu-Fu Chen; Wei-Shen Su; Chun-Hu Wu; Tsuo-Hung Lan; Feng-Yi Yang (Molecular Neurobiology, 2018)

A new polyoxygenated cyclohexene derivative from Artabotrys hainanensis - Jin-Ying Tang; Yan-Ping Liu; Peng-Kun Ju; Xiu-Lan Luo; Zhi-Jie Zhang; Peng Ren; Liang Lai; Guang-Ying Chen; Yan-Hui Fu (Natural Product Research, 2018)

Comparisons of cadmium bioaccumulation potentials and resistance physiology of Microsorum pteropus and Echinodorus grisebachii - Yun-Yun Yan; Jun-Jun Wang; Xin-Yu Lan; Qing-Mei Wang; Fu-Liu Xu (Environmental Science and Pollution Research, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

On the ratio of intercellular to ambient CO2 (c i/c a) derived from ecosystem flux - Zheng-Hong Tan; Zhi-Xiang Wu; Alice C. Hughes; Douglas Schaefer; Jiye Zeng; Guo-Yu Lan; Chuang Yang; Zhong-Liang Tao; Bang-Qian Chen; Yao-Hua Tian; Liang Song; Muhammad Tahir Jatoi; et al. (International Journal of Biometeorology, 2017)

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

The Study of Graph Measurements for Hub Identification in Multiple Parcellated Brain Networks of Healthy Older Adult - Cong Jin; Yi-Ping Chao; Lan Lin; Zhenrong Fu; Baiwen Zhang; Shuicai Wu (Journal of Medical and Biological Engineering, 2017)

Associations of rs3740677 within GAB2 Gene with LOAD in Chinese Han Population - Jing-Yu Zheng; Hui-Fu Wang; Yu Wan; Meng-Shan Tan; Chen-Chen Tan; Lin Tan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Effects of HLA-DRB1/DQB1 Genetic Variants on Neuroimaging in Healthy, Mild Cognitive Impairment, and Alzheimer’s Disease Cohorts - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Jinyuan Liu; Yu Wan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Genetic Association of HLA Gene Variants with MRI Brain Structure in Alzheimer’s Disease - Zi-Xuan Wang; Yu Wan; Lin Tan; Jinyuan Liu; Hui-Fu Wang; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

The epigenetic modifications and the anterior to posterior characterization of meiotic entry during mouse oogenesis - Xia-Fei Fu; Fan Yang; Shun-Feng Cheng; Yan-Ni Feng; Lan Li; Paul W. Dyce; Wei Shen; Xiao-Feng Sun (Histochemistry and Cell Biology, 2017)

Tissue-Specific Regulation of the Contents and Correlations of Mineral Elements in Hens by Zinc Oxide Nanoparticles - Yong Zhao; Yan-Ni Feng; Lan Li; Hong-Fu Zhang; Yu-Na Zhang; Peng-Fei Zhang; Xin-Qi Liu; Wei-Dong Zhang; Ting-Ting Huang; Li Zhao; Wei Shen; Zhi-Hui Hao (Biological Trace Element Research, 2017)

Rapid generation of genetic diversity by multiplex CRISPR/Cas9 genome editing in rice - Lan Shen; Yufeng Hua; Yaping Fu; Jian Li; Qing Liu; Xiaozhen Jiao; Gaowei Xin; Junjie Wang; Xingchun Wang; Changjie Yan; Kejian Wang (Science China Life Sciences, 2017)

Early-Life Social Isolation-Induced Depressive-Like Behavior in Rats Results in Microglial Activation and Neuronal Histone Methylation that Are Mitigated by Minocycline - Hong-Tao Wang; Fu-Lian Huang; Zhao-Lan Hu; Wen-Juan Zhang; Xiao-Qing Qiao; Yan-Qing Huang; Ru-Ping Dai; Fang Li; Chang-Qi Li (Neurotoxicity Research, 2017)

Association of DISC1 Polymorphisms with Late-Onset Alzheimer’s Disease in Northern Han Chinese - Xiao-Yan Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Ling-Li Kong; Zhan-Jie Zheng; Chen-Chen Tan; Wei Zhang; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; et al. (Molecular Neurobiology, 2017)

HLA-A2 Alleles Mediate Alzheimer’s Disease by Altering Hippocampal Volume - Zi-Xuan Wang; Hui-Fu Wang; Lin Tan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

SORL1 Is Associated with the Risk of Late-Onset Alzheimer’s Disease: a Replication Study and Meta-Analyses - Cheng-Cheng Zhang; Hui-Fu Wang; Meng-Shan Tan; Yu Wan; Wei Zhang; Zhan-Jie Zheng; Ling-Li Kong; Zi-Xuan Wang; Lin Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Effects of salinity on cold tolerance of Malaysian red tilapia - Yan-fu He; Lan-mei Wang; Wen-bin Zhu; Zai-jie Dong; Nian Liu (Aquaculture International, 2017)

Endovascular Treatment Versus Intravenous Thrombolysis for Acute Ischemic Stroke: a Quantitative Review and Meta-Analysis of 21 Randomized Trials - Chen-Chen Tan; Hui-Fu Wang; Jin-Long Ji; Meng-Shan Tan; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Impacts of CD33 Genetic Variations on the Atrophy Rates of Hippocampus and Parahippocampal Gyrus in Normal Aging and Mild Cognitive Impairment - Wen-Ying Wang; Ying Liu; Hui-Fu Wang; Lin Tan; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

A Missense Variant in TREML2 Reduces Risk of Alzheimer’s Disease in a Han Chinese Population - Teng Jiang; Yu Wan; Jun-Shan Zhou; Meng-Shan Tan; Qing Huang; Xi-Chen Zhu; Huan Lu; Hui-Fu Wang; Qi Chen; Lin Tan; Ying-Dong Zhang; Lan Tan; et al. (Molecular Neurobiology, 2017)

Effect of CR1 Genetic Variants on Cerebrospinal Fluid and Neuroimaging Biomarkers in Healthy, Mild Cognitive Impairment and Alzheimer's Disease Cohorts - Xi-Chen Zhu; Hui-Fu Wang; Teng Jiang; Huan Lu; Meng-Shan Tan; Chen-Chen Tan; Lin Tan; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

Association of Parkinson’s Disease GWAS-Linked Loci with Alzheimer’s Disease in Han Chinese - Xi-Chen Zhu; Lei Cao; Meng-Shan Tan; Teng Jiang; Hui-Fu Wang; Huan Lu; Chen-Chen Tan; Wei Zhang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

GWAS-Linked Loci and Neuroimaging Measures in Alzheimer’s Disease - Jie-Qiong Li; Hui-Fu Wang; Xi-Chen Zhu; Fu-Rong Sun; Meng-Shan Tan; Chen-Chen Tan; Teng Jiang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2017)

The Impact of UNC5C Genetic Variations on Neuroimaging in Alzheimer’s Disease - Jia-Hao Sun; Hui-Fu Wang; Xi-Chen Zhu; Wan-Jiang Yu; Chen-Chen Tan; Teng Jiang; Meng-Shan Tan; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2016)

Dietary Patterns and Risk of Dementia: a Systematic Review and Meta-Analysis of Cohort Studies - Lei Cao; Lan Tan; Hui-Fu Wang; Teng Jiang; Xi-Chen Zhu; Huan Lu; Meng-Shan Tan; Jin-Tai Yu (Molecular Neurobiology, 2016)

Redistribution of Cav2.1 channels and calcium ions in nerve terminals following end-to-side neurorrhaphy: ionic imaging analysis by TOF–SIMS - Chiung-Hui Liu; Hung-Ming Chang; To-Jung Tseng; Chyn-Tair Lan; Li-You Chen; Su-Chung Youn; Jian-Jr Lee; Fu-Der Mai; Jui-Feng Chou; Wen-Chieh Liao (Histochemistry and Cell Biology, 2016)

The heterogeneity of islet autoantibodies and the progression of islet failure in type 1 diabetic patients - Jin Liu; Lingling Bian; Li Ji; Yang Chen; Heng Chen; Yong Gu; Bingqin Ma; Wei Gu; Xinyu Xu; Yun Shi; Jian Wang; Dalong Zhu; et al. (Science China Life Sciences, 2016)

Multiple Effect of APOE Genotype on Clinical and Neuroimaging Biomarkers Across Alzheimer’s Disease Spectrum - Ying Liu; Lan Tan; Hui-Fu Wang; Yong Liu; Xiao-Ke Hao; Chen-Chen Tan; Teng Jiang; Bing Liu; Dao-Qiang Zhang; Jin-Tai Yu (Molecular Neurobiology, 2016)

Impact of Common Variations in PLD3 on Neuroimaging Phenotypes in Non-demented Elders - Chong Wang; Hui-Fu Wang; Meng-Shan Tan; Ying Liu; Teng Jiang; Dao-Qiang Zhang; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2016)

Education and Risk of Dementia: Dose-Response Meta-Analysis of Prospective Cohort Studies - Wei Xu; Lan Tan; Hui-Fu Wang; Meng-Shan Tan; Lin Tan; Jie-Qiong Li; Qing-Fei Zhao; Jin-Tai Yu (Molecular Neurobiology, 2016)

Antiviral activity of recombinant porcine surfactant protein A against porcine reproductive and respiratory syndrome virus in vitro - Lan Li; Qisheng Zheng; Yuanpeng Zhang; Pengcheng Li; Yanfeng Fu; Jibo Hou; Xilong Xiao (Archives of Virology, 2016)

Diagnostic values of osteopontin combined with CA125 for ovarian cancer: a meta-analysis - Zhu Lan; Dan Fu; Xiuzhang Yu; Mingrong Xi (Familial Cancer, 2016)

Chronic Metformin Preconditioning Provides Neuroprotection via Suppression of NF-κB-Mediated Inflammatory Pathway in Rats with Permanent Cerebral Ischemia - Xi-Chen Zhu; Teng Jiang; Qiao-Quan Zhang; Lei Cao; Meng-Shan Tan; Hui-Fu Wang; Zheng-Zheng Ding; Lan Tan; Jin-Tai Yu (Molecular Neurobiology, 2015)

l-Amino acid carbamate prodrugs of scutellarin: synthesis, physiochemical property, Caco-2 cell permeability, and in vitro anti-oxidative activity - Yu-Feng Cha; Shun Zhang; Hang Su; Yu Ou; Xiao-Zhong Fu; Feng-Jie Jiang; Yong-Long Zhao; Yong-Xi Dong; Min Luo; Yong Huang; Yan-Yu Lan; Ai-Min Wang; et al. (Medicinal Chemistry Research, 2015)

Interactions between household air pollution and GWAS-identified lung cancer susceptibility markers in the Female Lung Cancer Consortium in Asia (FLCCA) - H. Dean Hosgood; Minsun Song; Chao Agnes Hsiung; Zhihua Yin; Xiao-Ou Shu; Zhaoming Wang; Nilanjan Chatterjee; Wei Zheng; Neil Caporaso; Laurie Burdette; Meredith Yeager; Sonja I. Berndt; et al. (Human Genetics, 2015)

Anther development of maize (Zea mays) and longstamen rice (Oryza longistaminata) revealed by cryo-SEM, with foci on locular dehydration and pollen arrangement - Chih-Hua Tsou; Ping-Chin Cheng; Chiung-Maan Tseng; Hsiao-Jung Yen; Yu-Lan Fu; Tien-Rong You; David B. Walden (Plant Reproduction, 2015)

Ischemic Preconditioning Provides Neuroprotection by Induction of AMP-Activated Protein Kinase-Dependent Autophagy in a Rat Model of Ischemic Stroke - Teng Jiang; Jin-Tai Yu; Xi-Chen Zhu; Qiao-Quan Zhang; Meng-Shan Tan; Lei Cao; Hui-Fu Wang; Jian-Quan Shi; Li Gao; Hao Qin; Ying-Dong Zhang; Lan Tan (Molecular Neurobiology, 2015)

Different secondary metabolic responses to MeJA treatment in shikonin-proficient and shikonin-deficient cell lines from Arnebia euchroma (Royle) Johnst - Sheng Wang; Lan Ping Guo; Teng Xie; Jian Yang; Jin Fu Tang; Xuan Li; Xiao Wang; Lu Qi Huang (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Primordial follicle assembly was regulated by notch signaling pathway in the mice - Chun-Lei Chen; Xia-Fei Fu; Lin-Qing Wang; Jun-Jie Wang; Hua-Gang Ma; Shun-Feng Cheng; Zhu-Mei Hou; Jin-Mei Ma; Guo-Bo Quan; Wei Shen; Lan Li (Molecular Biology Reports, 2014)

A Novel Co-immunoprecipitation Protocol Based on Protoplast Transient Gene Expression for Studying Protein–protein Interactions in Rice - Jia Wei Yang; Jia Xin Fu; Jing Li; Xiao Ling Cheng; Feng Li; Jing Fang Dong; Zhen Lan Liu; Chu Xiong Zhuang (Plant Molecular Biology Reporter, 2014)

The cell cycle distribution should be given more consideration in cell-based in vitro toxicological studies - Peng Zhao; Juanling Fu; Biyun Yao; Yanchao Song; Lan Yuan; Yongrui Jia; Shiliang Ma; Wen Chen; Zongcan Zhou (Archives of Toxicology, 2014)

Age-dependent association of KIBRA gene polymorphism with Alzheimer’s disease in Han Chinese - Hui-Fu Wang; Lan Tan; Jin-Tai Yu; Xiao-Ying Ma; Qiu-Yan Liu; Wei Wang (Molecular Biology Reports, 2013)

Genetic structure and association mapping of cold tolerance in improved japonica rice germplasm at the booting stage - Di Cui; Chang-ying Xu; Cui-feng Tang; Chun-gang Yang; Teng-qiong Yu; Xin-xiang A; Gui-lan Cao; Fu-rong Xu; Jun-guo Zhang; Long-zhi Han (Euphytica, 2013)

QTL mapping and correlation analysis for 1000-grain weight and percentage of grains with chalkiness in rice - JIAN-MIN BIAN; HUAN SHI; CUI-JUAN LI; CHANG-LAN ZHU; QIU-YING YU; XIAO-SONG PENG; JUN-RU FU; XIAO-PENG HE; XIAO-RONG CHEN; LI-FANG HU; LIN-JUAN OUYANG; HAO-HUA HE (Journal of Genetics, 2013)

Association of TOMM40 Polymorphisms with Late-Onset Alzheimer’s Disease in a Northern Han Chinese Population - Xiao-Ying Ma; Jin-Tai Yu; Wei Wang; Hui-Fu Wang; Qiu-Yan Liu; Wei Zhang; Lan Tan (NeuroMolecular Medicine, 2013)

Acute Clenbuterol Induces Hypotension, Atrioventricular Block and Cardiac Asystole in the Rabbit - Yan Ke; Li-Lan Fu; Xia-Fei Hong; Run Dong; Tian-Ming Xu; Jing-Fei Guo; Yan Liu; Ji-Min Cao (Cardiovascular Toxicology, 2013)

Association between mandibular posterior alveolar morphology and growth pattern in a Chinese population with normal occlusion - Min Han; Rong-yang Wang; Hong Liu; Xiu-juan Zhu; Fu-lan Wei; Tao Lv; Na-na Wang; Li-hua Hu; Guo-ju Li; Dong-xu Liu; Chun-ling Wang (Journal of Zhejiang University-SCIENCE B, 2013)

Effect of dehydroepiandrosterone administration on recovery from mix-type exercise training-induced muscle damage - Yi-Hung Liao; Kun-Fu Liao; Chung-Lan Kao; Chung-Yu Chen; Chih-Yang Huang; Wei-Hsiang Chang; John L. Ivy; Jeffrey R. Bernard; Shin-Da Lee; Chia-Hua Kuo (European Journal of Applied Physiology, 2013)

Tetrodotoxin attenuates isoproterenol-induced hypertrophy in H9c2 rat cardiac myocytes - Ming-Zi Chen; Qing-Ting Bu; Shu-Chao Pang; Feng-Lan Li; Mei-Na Sun; Er-Fu Chu; Hui Li (Molecular and Cellular Biochemistry, 2012)

Characteristic, composition, and sources of TSP investigated by HRTEM/EDS and ESEM/EDS - Yunbo Zhai; Zongmin Fu; Lafang Wang; Guangming Zeng; Caiting Li; Hongmei Chen; Yuanming Lan; Pei Lu (Environmental Monitoring and Assessment, 2012)

The effects of hypoxia acclimation, exercise training and fasting on swimming performance in juvenile qingbo (Spinibarbus sinensis) - Wen-Wen Zhao; Xu Pang; Jiang-Lan Peng; Zhen-Dong Cao; Shi-Jian Fu (Fish Physiology and Biochemistry, 2012)

Effects of three different PAHs on nitrogen-fixing bacterial diversity in mangrove sediment - Fu-Lin Sun; You-Shao Wang; Cui-Ci Sun; Ya-Lan Peng; Chao Deng (Ecotoxicology, 2012)

Genetic variant in TP63 on locus 3q28 is associated with risk of lung adenocarcinoma among never-smoking females in Asia - H. Dean Hosgood; Wen-Chang Wang; Yun-Chul Hong; Jiu-Cun Wang; Kexin Chen; I-Shou Chang; Chien-Jen Chen; Daru Lu; Zhihua Yin; Chen Wu; Wei Zheng; Biyun Qian; et al. (Human Genetics, 2012)

Effects of the duration of expressions on the recognition of microexpressions - Xun-bing Shen; Qi Wu; Xiao-lan Fu (Journal of Zhejiang University-SCIENCE B, 2012)

The Ran-binding protein RanBPM can depress the NF-κB pathway by interacting with TRAF6 - Lan Wang; Chengbo Fu; Yingbin Cui; Yunfei Xie; Yuhe Yuan; Xin Wang; Hong Chen; Bing-Ren Huang (Molecular and Cellular Biochemistry, 2012)

Three-dimensional evaluation of upper anterior alveolar bone dehiscence after incisor retraction and intrusion in adult patients with bimaxillary protrusion malocclusion - Qing-yuan Guo; Shi-jie Zhang; Hong Liu; Chun-ling Wang; Fu-lan Wei; Tao Lv; Na-na Wang; Dong-xu Liu (Journal of Zhejiang University-SCIENCE B, 2011)

Isolation and characterization of an antimicrobial peptide from bovine hemoglobin α-subunit - Jianhe Hu; Minglu Xu; Bolin Hang; Lan Wang; Qing Wang; Junjie Chen; Tao Song; Dengfeng Fu; Ziliang Wang; Sanhu Wang; Xingyou Liu (World Journal of Microbiology and Biotechnology, 2011)

Characterization of a ZmSERK gene and its relationship to somatic embryogenesis in a maize culture - Suzhi Zhang; Xinggui Liu; Yueai Lin; Guangning Xie; Fengling Fu; Hailan Liu; Jing Wang; Shibin Gao; Hai Lan; Tingzhao Rong (Plant Cell, Tissue and Organ Culture (PCTOC), 2011)

Enhanced γ-aminobutyric acid-forming activity of recombinant glutamate decarboxylase (gadA) from Escherichia coli - Qi Wang; Yinqiang Xin; Feng Zhang; Zhiyong Feng; Jin Fu; Lan Luo; Zhimin Yin (World Journal of Microbiology and Biotechnology, 2011)

A large indel mutation of the bovine ADD1/SREBP1c gene and its effects on growth traits in some native cattle breeds from China - Yong-Zhen Huang; En-Ping Zhang; Jing Wang; Yong-Tao Huai; Liang Ma; Fu-Ying Chen; Xian-Yong Lan; Chu-Zhao Lei; Xing-Tang Fang; Ju-Qiang Wang; Hong Chen (Molecular Biology Reports, 2011)

Involvement of recF in 254 nm Ultraviolet Radiation Resistance in Deinococcus radiodurans and Escherichia coli - Xiaosong Chang; Lan Yang; Qing Zhao; Wenjuan Fu; Hao Chen; Zhiqun Qiu; Ji-an Chen; Ran Hu; Weiqun Shu (Current Microbiology, 2010)

Dipyrithione inhibits IFN-γ-induced JAK/STAT1 signaling pathway activation and IP-10/CXCL10 expression in RAW264.7 cells - Cui Han; Jin Fu; Ziwen Liu; Huang Huang; Lan Luo; Zhimin Yin (Inflammation Research, 2010)

NP-184[2-(5-methyl-2-furyl) benzimidazole], a novel orally active antithrombotic agent with dual antiplatelet and anticoagulant activities - Heng-Lan Kuo; Jin-Cherng Lien; Ching-Hu Chung; Chien-Hsin Chang; Shyh-Chyi Lo; I-Chun Tsai; Hui-Chin Peng; Sheng-Chu Kuo; Tur-Fu Huang (Naunyn-Schmiedeberg's Archives of Pharmacology, 2010)

The metabolic responses and acid–base status after feeding, exhaustive exercise, and both feeding and exhaustive exercise in Chinese catfish (Silurus asotus Linnaeus) - Ke-Gui Li; Zhen-Dong Cao; Jiang-Lan Peng; Shi-Jian Fu (Journal of Comparative Physiology B, 2010)

Cationic liposome coupled endostatin gene for treatment of peritoneal colon cancer - Keng-Li Lan; Fu Ou-Yang; Sang-Hue Yen; How-Ling Shih; Keng-Hsin Lan (Clinical & Experimental Metastasis, 2010)

Magnesium sulfate enhances exercise performance and manipulates dynamic changes in peripheral glucose utilization - Shiu-Min Cheng; Lin-Lan Yang; Sy-Huah Chen; Mei-Hsiang Hsu; I-Ju Chen; Fu-Chou Cheng (European Journal of Applied Physiology, 2010)

Erratum to: Bioinformatics Analysis of Lactoferrin Gene for Several Species - Jing-Fen Kang; Xiang-Long Li; Rong-Yan Zhou; Lan-Hui Li; Fu-Jun Feng; Xiu-Li Guo (Biochemical Genetics, 2009)

The effect of exhaustive chasing training and detraining on swimming performance in juvenile darkbarbel catfish (Peltebagrus vachelli) - Yun Liu; Zhen-Dong Cao; Shi-Jian Fu; Jiang-Lan Peng; Yu-Xiang Wang (Journal of Comparative Physiology B, 2009)

Development and characterization of a new 1BL.1RS translocation line with resistance to stripe rust and powdery mildew of wheat - Tian-Heng Ren; Zu-Jun Yang; Ben-Ju Yan; Huai-Qiong Zhang; Shu-Lan Fu; Zheng-Long Ren (Euphytica, 2009)

Detrital zircon evidence for the antiquity of Taiwan - Ching-Ying Lan; Tadashi Usuki; Kuo-Lung Wang; Tzen-Fu Yui; Kazuaki Okamoto; Yuan-Hsi Lee; Takafumi Hirata; Yoshitaka Kon; Yuji Orihashi; Juhn G. Liou; Chun-Sun Lee (Geosciences Journal, 2009)

Early Paleozoic medium-pressure metamorphism in central Vietnam: evidence from SHRIMP U-Pb zircon ages - Tadashi Usuki; Ching-Ying Lan; Tzen-Fu Yui; Yoshiyuki Iizuka; Tich Van Vu; Tuan Anh Tran; Kazuaki Okamoto; Joseph L. Wooden; Juhn G. Liou (Geosciences Journal, 2009)

Gender difference in the effect of daytime sleep on declarative memory for pictures - Bo Wang; Xiao-lan Fu (Journal of Zhejiang University-SCIENCE B, 2009)

Previous pulmonary disease and family cancer history increase the risk of lung cancer among Hong Kong women - Xiao-Rong Wang; Ignatius T. S. Yu; Yuk Lan Chiu; Hong Qiu; Zhenming Fu; William Goggins; Joseph S. K. Au; Lap-Ah Tse; Tze-Wai Wong (Cancer Causes & Control, 2009)

EGb761 Protects Hydrogen Peroxide-induced Death of Spinal Cord Neurons through Inhibition of Intracellular ROS Production and Modulation of Apoptotic Regulating Genes - Xiaoyan Jiang; Baoming Nie; Saili Fu; Jianguo Hu; Lan Yin; Lin Lin; Xiaofei Wang; Peihua Lu; Xiao-Ming Xu (Journal of Molecular Neuroscience, 2009)

Effect of meal size on excess post-exercise oxygen consumption in fishes with different locomotive and digestive performance - Shi-Jian Fu; Ling-Qing Zeng; Xiu-Ming Li; Xu Pang; Zhen-Dong Cao; Jiang-Lan Peng; Yu-Xiang Wang (Journal of Comparative Physiology B, 2009)

Characterization and SNP Identification of Part of the Goat Melanophilin Gene - Fu-Jun Feng; Xiang-Long Li; Rong-Yan Zhou; Gui-Ru Zheng; Lan-Hui Li; Dong-Feng Li (Biochemical Genetics, 2009)

The application of ultrasound in the management of cerebral arteriovenous malformation - Bing Fu; Ji-Zong Zhao; Lan-Bing Yu (Neuroscience Bulletin, 2008)

Variation of 423G>T in the Agouti Gene Exon 4 in Indigenous Chinese Goat Breeds - Chun-Juan Tang; Rong-Yan Zhou; Xiang-Long Li; Jing-Wen Zhao; Lan-Hui Li; Fu-Jun Feng; Dong-Feng Li; Jian-Tao Wang; Xiu-Li Guo; Jing-Fen Keng (Biochemical Genetics, 2008)

Specific leaf area relates to the differences in leaf construction cost, photosynthesis, nitrogen allocation, and use efficiencies between invasive and noninvasive alien congeners - Yu-Long Feng; Gai-Lan Fu; Yu-Long Zheng (Planta, 2008)

Nitrogen allocation, partitioning and use efficiency in three invasive plant species in comparison with their native congeners - Yu-Long Feng; Gai-Lan Fu (Biological Invasions, 2008)

Bioinformatics Analysis of Lactoferrin Gene for Several Species - Jing-Fen Kang; Xiang-Long Li; Rong-Yan Zhou; Lan-Hui Li; Fu-Jun Feng; Xiu-Li Guo (Biochemical Genetics, 2008)

A novel thioredoxin reductase inhibitor inhibits cell growth and induces apoptosis in HL-60 and K562 cells - Zuo-fu Peng; Lin-xiang Lan; Fang Zhao; Jing Li; Qiang Tan; Han-wei Yin; Hui-hui Zeng (Journal of Zhejiang University-SCIENCE B, 2008)

Analyses of the seed protein contents on the cultivated and wild buckwheat Fagopyrum esculentum resources - Yu-Zhen Guo; Qing-Fu Chen; Lan-Ying Yang; Yun-Hua Huang (Genetic Resources and Crop Evolution, 2007)

Effects of moderate and severe intermittent hypoxia on vascular endothelial function and haemodynamic control in sedentary men - Jong-Shyan Wang; Liang-Yu Chen; Li-Lan Fu; Mei-Ling Chen; May-Kuen Wong (European Journal of Applied Physiology, 2007)

Norepinephrine induces apoptosis in neonatal rat endothelial cells via a ROS-dependent JNK activation pathway - Yun-Ching Fu; Sui-Chu Yin; Ching-Shiang Chi; Betau Hwang; Shih-Lan Hsu (Apoptosis, 2006)

Soil microbial biomass as affected by non-flooded plastic mulching cultivation in rice - Yong-Shan Li; Liang-Huan Wu; Xing-Hua Lu; Li-Mei Zhao; Qiao-Lan Fan; Fu-Suo Zhang (Biology and Fertility of Soils, 2006)

Effect of meal size on postprandial metabolic response in Chinese catfish (Silurus asotus Linnaeus) - Shi-Jian Fu; Zhen-Dong Cao; Jiang-Lan Peng (Journal of Comparative Physiology B, 2006)

A nonlinear coupled soil moisture-vegetation model - Liu Shikuo; Liu Shida; Fu Zuntao; Sun Lan (Advances in Atmospheric Sciences, 2005)

Inhibition of endogenous trypsin- and chymotrypsin-like activities in transgenic lettuce expressing heterogeneous proteinase inhibitor SaPIN2a - Zeng-Fu Xu; Whei-Lan Teng; Mee-Len Chye (Planta, 2004)

Digestion Methods for Total Heavy Metals in Sediments and Soils - Zeng-Yei Hseu; Zueng-Sang Chen; Chen-Chi Tsai; Chun-Chih Tsui; Shuang-Fu Cheng; Chyan-Lan Liu; Haw-Tarn Lin (Water, Air, & Soil Pollution, 2002)